GBIF Occurrence Download - Occdownload Gbif.Org (The Global Biodiversity Information Facility, 2015)
A dataset containing 526034780 species occurrences available in GBIF matching the query: All data. The dataset includes 526034780 records from 12678 constituent datasets: 11371 records from Mammal specimens. 661 records from Green Algae. 36871 records from LSUMZ Mammals Collection. 59 records from Im Bauerngarten. 161 records from Schussenaue bei Berg. 110 records from Obstwiese Osterberg. 908 records from Spider (JNHM-SP). 489 records from Galapagos grasses and sedges. 670 records from Pilstingermoos. 460 records from Unna-Mühlhausen, Wiesen. 309632 records from CAS Herpetology (HERP). 3537 records from ATCC Bacteria Collection Catalog. 36992 records from Vascular Plants Collection of Sagamihara City Museum. 470 records from Gewann Krampf (Heilbronn). 457 records from Microbial Observatory of the Laboratoire Arago. 1238 records from Insect Collection (CeStuBio). 5 records from A new species and records of Diolenius Thorell, 1870 (Araneae: Salticidae) from New Guinea. 26882 records from KUBI Ornithology Tissue Collection. 1 records from Eremaeus hepaticus. 22 records from Bacteria Collection of the Seto Marine Biological Laboratory, Kyoto University. 181 records from Alien Species in Poland - Animals. 101 records from (Table 4a) Downcore distribution of live benthic foraminifera of sediment core SW_3a, California continental borderland. 83 records from Occurrence of mammalia relicts at site Spitzbubenhöhle. 1 records from A new Camponotus from Madagascar and a small collection of ants from Mauritius.. 150 records from Birdrace-Ostseevögel-Ostvorpommern. 79 records from Balkon (Norderstedt). 29111 records from Online Atlas of vascular plants 2012-2020. 1 records from Hoplophora laevigata. 76 records from (Fig. 2) Vertical density profiles of meiofauna taxa in surface sediments of Potter Cove, King George Island, Antarctic Peninsula. 3945 records from TTRS Ornithology. 484594 records from Field Museum of Natural History (Zoology) Bird Collection. 2172 records from Coleccin de Reptiles. 1130 records from Ostracoda in sediment core PS51/154-11. 5729 records from Alterra (NL) - Entomofauna inventory in cattle grazed dune grassland. 38 records from The Oriental species of the ant genus Probolomyrmex (Insecta: Hymenoptera: Formicidae: Proceratiinae).. 93 records from (Table 5) Oligocene to Pleistocene nannofossil range chart for ODP Hole 134-829A. 358 records from (Appendix D) Benthic foraminiferal census data for extinction, uniserial survivor and high-flux, low-oxygen tolerant groups for ODP Site 161-975. 69982 records from Lepidoptera collection, Natural History Museum, University of Oslo. 644 records from (Table T1) Planktonic foraminiferal stratigraphy of ODP Hole 173-1065A sediments. 960 records from (Table 4) Relative abundances of stratigraphically useful planktonic foraminifers from ODP Site 167-1013 sediments. 3 records from Diatom abundance of Hole 38-338, Part 2. 251744 records from Instituto Nacional de Pesquisas da Amazônia (INPA) - Herbarium. 15956 records from Algae (S). 28370 records from UAM Bird Collection (Arctos). 108 records from (Table 7) Planktonic foraminifera species in bottom sediments of Core ML5_348, North Atlantic. 19 records from The first case of aggressive mimicry among lamprologines in a new species of Lepidiolamprologus (Perciformes: Cichlidae) from Lake Tanganyika.. 33 records from (Table 1) CTD data, mean spring and annual temperatures and salinities from World Ocean Atlas (WOA, 2001), and Mg/Ca data, sampled with a multinet at station 74 and 81 from RV Poseidon cruise 334. 6 records from Der Wiesenpark in Oschersleben - ein Arboretum mit eigener Ästhetik. 19 records from Goethe-Hauptschule/Projekt I-10. 214 records from Binsenwiesen. 217 records from Birdrace-Ornis_im_Einsatz-Lahn-Dill-Kreis. 58 records from Schulgelände Kranich-Gymnasium (Salzgitter). 7 records from Stadtrandlandschaft Apolda-Nord. 139 records from BIRDRACE Turbine Untersee. 166 records from BIRDRACE Die Düsselmöwen. 123 records from BIRDRACE INTERNETLITHO feat Fliegende Füchse. 62 records from Lebensraum Dorf. 71 records from tab3. 163 records from Entomofauna laguna El Tinije. 3065 records from Colección de Ofidios Museo de La Salle Bogotá (MLS). 305 records from Rohrmeistereiplateau und angrenzendes Gebiet. 56 records from (Appendix A) Pollen and spore counts at DSDP Hole 64-480. 138 records from Total foraminifera counts of multinet M11/1_MSN520. 2775 records from CeDoc de Biodiversitat Vegetal: BCN- Algues de J. Rodríguez Femenías. 397 records from Benthic foraminifera counts of sediment core GIK23353-5. 75 records from Total foraminifera counts of multinet M12/3_MSN562. 147 records from Total foraminifera counts of multinet M36/6_MSN1195. 131 records from Total foraminifera counts of multinet PO247/2_MSN1377. 9 records from Phytoplankton abundance at station Casma_2003-01-30_1, Casma, Peru. 9 records from Nematode genera abundances at the Arctic Håkon Mosby Mud Volcano (HMMV) of sediment core PS64/312-1. 213 records from Coccoliths in sediment core PS1113-1. 52 records from Nanoplankton abundance at station GeoB2017-4. 7 records from Schulhof A.-Schweitzer Schule (Wetzlar). 33 records from Assemblage of living benthic foraminifera in sediment core SO118_MC-35, 30-63 µm fraction. 5110 records from Live benthic foraminifera in South Atlantic surface sediments. 596 records from Lower Albian l`Arboudeysse section (Niveau Paquier) individuals per gram sediment of benthic foraminifera, in SE France. 174 records from Total foraminifera counts from multinet M31/3_MSN915. 227 records from Total foraminifera counts from multinet M31/3_MSN918. 40 records from (Supplementary Table 2) Estimates of bottom-water oxygenation at site GeoB11185-1. 169 records from Abundance of planktic foraminifera at CTD station PS55/051. 215 records from (Table 2) Distribution of sinsitral and dextral fohsellids in middle Miocene sediments of ODP Hole 130-806B from the Ontong Java Plateau, Pacific Ocean. 25 records from Heavy minerals of sediment core PL94-08. 24 records from Occurrence of mammalia relicts at site Fuchsloch im Krockstein. 33 records from Total foraminifera counts from M35/1_MSN1053. 120 records from Total foraminifera counts of multinet M10/2_MSN319. 109 records from Total foraminifera counts of multinet M21/2_MSN642. 88 records from Total foraminifera counts of multinet PO247/2_MSN1384. 107 records from Content of coarse fraction and G. menardii in sediment corev V26-102. 8 records from Large protozoa abundance measured on concentrated water bottle samples at station PS58/046-5. 4 records from Microzooplankton abundance and biomass at station TT054_13-18. 3 records from Sarcodine counts and carbon biomass at station TT011_9-CTD115. 11250 records from El Censo Neotropical de Aves Acuáticas en Colombia (CNAA): 2002 - 2011. 7 records from Abundance of nematoda in sediment profile M3/1_031 from the Iberian deep sea basin (Table 5). 142 records from Total foraminifera counts of multinet M21/3_MSN675. 2629628 records from Continuous Plankton Recorder Dataset (SAHFOS). 12 records from Large protozoa abundance measured on concentrated water bottle samples at station PS58/091-3. 11 records from Microzooplankton abundance and biomass at station TT043_27-1. 4 records from Nano and microzooplankton abundance and biomass at station NBP97-01-17-7. 11 records from Distribution of meiobenthos in sediment core M19_232-2 of the northeastern Atlantic (Table 1). 5 records from Distribution of meiobenthos in sediment core M19_216-2 (2) of the northeastern Atlantic (Table 1). 83 records from Nematode genera abundances at the Arctic Håkon Mosby Mud Volcano (HMMV) of sediment core PS64/390-1c. 10 records from (Table 2) Abundance of benthic foraminifers of sediment core PS2161-1. 182 records from Biotope entdecken im Kockmecker Siepen (Sauerland). 45080 records from A Biological Survey of the Waters of Woods Hole and Vacinity. 95 records from Plasm bearing foraminifera counts of multinet M21/2_MSN624. 78 records from Phytoplankton counted on two fractions of surface sediment samples from Meteor stations M35003-4 to M35010-3. 5 records from Microorganism Abundance Data from the Northeast Pacific. 4 records from Sarcodine counts and carbon biomass at station TT008_5-PMOC3. 6 records from Microzooplankton abundance and biomass at station NBP97-08-19-1. 12230 records from MfN - Fossil invertebrates IIb. 2 records from Nannofossil abundance of Hole 3-14. 14 records from Nannofossil abundance of Hole 26-258. 85 records from (Table 5) Abundance of selected helicoliths at DSDP Site 82-563 in the North Atlantic. 1 records from Beitrage zur Kenntniss paläarctischer Myriopoden. XV. Aufsatz: Lithobiiden aus Bosnien, Herzogovina und Dalmatien. 599 records from Planktic foraminifera counts of sediment core V26-41. 61 records from BIRDRACE Bergische Ornis. 32 records from Grundschüler erkunden Schulumgebung. 1297 records from Dinoflagellate assemblage in surface sediments of the South Atlantic. 8 records from Size fractioned abundances and carbon biomasses of heterotrophic protists at station NIOP-B1_276-1. 21 records from Abundance and carbon biomass of phytoplankton at station TT008_5-CTD50. 22 records from Phytoplankton abundance at bottle station GOM2/7. 8 records from Phytoplankton abundance at station Casma_2003-02-27_1, Casma, Peru. 4 records from Distribution of meiobenthos in sediment core M19_216-2 of the northeastern Atlantic (Table 1). 44 records from Coccolith counts of multinet M32/5_MSN974. 1 records from Benthic hard-bottom communities abundance at Lilliguapy in 2011. 3 records from Nannofossil abundance of Hole 10-93. 2 records from Nannofossil abundance of Hole 7-64A. 19 records from Nannofossil abundance of Hole 94-610A. 4 records from Range table from nannofossils in ODP Hole 198-1207B. 4054 records from Computarización de la Colección de helmintos parásitos de peces del estado de Tabasco. 236 records from (Table 6) Ostracod assemblages of sediment core 9409. 146 records from Phytoplankton abundance at station DI182_11862#3. 2 records from Nannofossil abundance of Hole 6-49. 456 records from (Appendix B) Benthic foraminiferal census data for extinction, uniserial survivor and high-flux, low-oxygen tolerant groups for ODP Hole 160-966B. 126 records from Nannofossil abundance of Hole 39-357. 343 records from Collection Cnidaria - ZMB. 3 records from Antarctic Arrow worms. 374843 records from BSBI tetrad data for Ireland. 15 records from Molluscs in surface sediments off Sylt collected during Heincke cruise HE278. 19 records from (Table S2) Nannofossil abundances at DSDP Hole 86-577A. 29 records from Nannofossil abundance of Hole 29-282. 2 records from Nannofossil abundance of Hole 1-5. 7319 records from Coleoptera. 16 records from Nannofossil abundance of Hole 57-438. 758888 records from Flora Atlas N.T.. 1966 records from Relative abundance of Neogene nannofossils at ODP Site 165-999 from the Caribbean. 5 records from Distribution of Quinqueloculina sp. in sediment core 13078-017. 73 records from Macrofauna abundance in surface sediment sampled during cruise DI222/2. 577 records from Estación Experimental de Zonas Áridas (CSIC): EEZA-Herpet. 99322 records from Royal Botanic Garden Edinburgh Living Plant Collections (E). 5995 records from Insect (HUNM-IN). 219 records from INERA-Luki reservation herbarium (CABIN project). 57 records from Nannofossil abundance in sediment core PS1311-4. 4909 records from (Table 4) Percentages of planktonic foraminiferal taxa from the 214 surface-sediment samples from the South China Sea and the western Pacific. 449 records from (Table 1) Abundance of dead benthic foraminifera in surface sediments of the Arctic Ocean. 5415 records from Coleopteran specimens of Iwate Prefectural Museum. 311 records from (App 1) Relative contents of mass species of benthic foraminifera in Holocene sediments from Core ASV11-880-3. 726 records from (Table 15) Distribution of planktonic foraminifera in the early to early late Oligocene section of ODP Hole 149-900A. 69959 records from Marine and Coastal Management - Linefish Dataset (Second Semester of 1998) (AfrOBIS). 7432 records from University of Alberta Museums, Ornithology Collection. 58 records from (Table 4) Relative abundance of selected benthic foraminifera in ODP Hole 104-642D. 310 records from (Table 2) Distribution of main species of planktonic foraminifers in Core AMK21-2179, Woodlark Basin. 1122 records from (Figure 2) Stratigraphic distribution of planktonic foraminifera in the Neogene of ODP Hole 122-762B. 54 records from Species occurring in the mytilid and alvinellid communities within the 9°N hydrothermal field at the East Pacific Rise. 19 records from (Table 4) Distribution and relative abundance of planktonic foraminifers in ODP Hole 114-704B. 929 records from Flora acuática vascular de las regiones hidrológicas R66 (Lagos Cráter del Nevado de Toluca) y R67 (Río Amacuzac-Lagunas de Zempoala), México. 6 records from Rango, comportamiento, tamaño de población y conservación de felinos en el Volcán de Colima. 1617 records from Análisis de la heterogeneidad ambiental y conectividad de las áreas naturales del sur del Valle de México_1. 9 records from Akita Prefectural Museum＋Cephalaspidomorphs Specimens of Akita Prefectural Museum. 17355 records from Ibaraki Nature Museum,Lichen collection. 815 records from Abundance of benthic infauna in surface sediments from the North Sea sampled during Belgica cruise BG86/1. 1128 records from (App 9) Relative contents of planktonic foraminifera species in sediments from Core NAST. 1871 records from Registros biológicos de especies de fauna vertebrada terrestre en la central hidroeléctrica Miel I - 2009. 8269 records from Insect Collection of Saitama Museum of Natural History. 270 records from (Table 2) Distribution of planktonic foraminiferal species in bottom sediments from Core LV28-42-5, Sea of Okhotsk. 26721 records from Bird Observational Records. 81490 records from Marine and Coastal Management - Linefish Dataset (First Semester of 1995) (AfrOBIS). 28 records from The Provincial Museum of Newfoundland and Labrador Natural History Collection. 17788 records from Fungal Specimens collected by HabitatVision (Jacob Heilmann-Clausen). 598 records from CECT Spanish Type Culture Collection(Bacteria). 10 records from (Table 2.2.1.1) Abundance of sympagic meiofauna of sea-ice core IO-14. 2 records from Akita Prefectural Museum＋Specimens of Class Pycnogonida of Akita Prefectural Museum. 731 records from Ibaraki Nature Museum, Mammals collection. 248680 records from Swiss National Orthoptera Databank. 36116 records from Fish Collection of Yokosuka City Museum. 145786 records from Vertebrate Zoology Division - Ornithology, Yale Peabody Museum. 812 records from Planktic foraminifera abundance of Hole 94-607. 504 records from Range table from benthic foraminifers in ODP Hole 172-1057A. 183 records from Range table from benthic foraminifers in ODP Hole 146-891B. 3 records from Dinoflagellate abundance of Hole 85-572A. 761 records from Abundance of benthic infauna in surface sediments from the North Sea sampled during Walther Herwig cruise WH220. 868 records from The Deepwater Program: Northern Gulf of Mexico Continental Slope Habitat and Benthic Ecology - DgoMB:Isopods. 1824 records from CNAN/Scorpiones. 1655 records from Derbyshire (Derby Museum) Biological Records Centre - Derbyshire REPTILE Records 1950-2007. 408 records from Visual Plants (144.41.33.158) - Private collection of Rainer Bussmann. 389 records from (Table 2) Distribution of planktonic foraminifera in DSDP Hole core 90-594. 2988 records from Distribution of planktic foraminifers of core Y71-09-101. 630 records from Relative abundance of planktic foraminifera in the 120 kyr time slice reconstruction of sediment core V29-179. 530 records from Nemertina World Checklist. 156 records from Botanischer Garten (Saarbrücken). 282 records from Faberpark (Nürnberg/Stein). 28 records from Microplankton abundance in the euphotic zone of the Aegean Sea at Station MARCH-94-GN3619940280100320. 15 records from Occurrence of mammalia relicts at site le gisemnet de Fongabon. 12 records from Planktic foraminifera abundance of Hole 42-372. 235 records from Fig. 4. Simplified macrofossil concentration in sediment core Lz1116. 9649 records from Bolus Herbarium Algal Specimen Database (AfrOBIS). 1902 records from Water Colours of Fungi by Fritz Wohlfarth at the Botanische Staatssammlung München. 37641 records from Nordic Genetic Resources. 976457 records from EURISCO, The European Genetic Resources Search Catalogue. 2955 records from (Table1) Abundance of planktonic foraminifera in DSDP Hole 75-532. 426 records from Planktic foraminifera assemblage in sediment core GIK23419-8. 489 records from ANTXXIII-8 Birds and Mammals. 98 records from Distribution of planktonic foraminifera in DSDP Hole 90-594 east of New Zealand. 336 records from KARSTLANDSCHAFT SÜDHARZ - VOM GIPSABBAU BEDROHT (Grenzstreifen am Röseberg). 1796 records from Sea shell specimens database of Mr. Toru Ueda collection, Shizuoka Prefecture Museum of Natural History. 4456 records from Colección de Artrópodos de la Asociación BIGA para el estudio del patrimonio natural de Galicia: ABIGA. 684 records from Percentages of planktonic foraminifera species in sediment core V23-110. 1008 records from Relative abundance of planktic foraminifera in the 120 kyr time slice reconstruction of sediment core V22-196. 199 records from Relative abundance of planktic foraminifera in the 120 kyr time slice reconstruction of sediment core V28-14. 354 records from Foraminifera distribution of sediment core KS310. 289 records from Summary of ecologically and stratigraphically important foraminifera in surface samples of the NW African continental margin (Table 3). 5 records from Analyses of the recent components of sediment core PS1014-1. 87075 records from Banc de dades de biodiversitat de Catalunya-ArtroCat. 194 records from Distribution of planktic foraminifera of sediment core GIK23259-2. 3978 records from Colección de Entomopatógenos de México (CNRCB). 1913 records from (Appendix B2) Distribution of planktic foraminifera in ODP Hole 181-1125A east of New Zealand. 98 records from Planktic foraminifera abundance of Hole 74-528. 651 records from Planktic foraminifera abundance of Hole 9-78. 251 records from Planktic foraminifera abundance of Hole 71-513A. 400 records from Planktic foraminifera abundance of Hole 32-310. 1075 records from (Tab. 12) Distribution of benthic foraminifera in Lower Cretaceous sediments of DSDP Hole 32-305, Shatsky Rise southeast of Japan. 362 records from Benthic foraminifera abundance of Hole 48-400A. 4 records from Occurrence of mammalia relicts at site Henauhof NW 2. 151 records from Meiobenthic taxon counts from deep-sea in situ recolonization experiment I deployed at station PS64/474-1 during ARK-XIX/3c. 64 records from Occurrence of mammalia relicts at site Spitalhöhle. 11 records from Radiolaria assemblage in sediment core GIK23414-6. 26 records from Planktic foraminifera abundance of Hole 20-200A. 84 records from Range table from planktonic foraminifers in ODP Hole 141-859B. 542 records from Range table from planktonic foraminifers in ODP Hole 182-1127B. 63 records from Range table from benthic foraminifers in ODP Hole 172-1062B. 31 records from Range table from benthic foraminifers in ODP Hole 181-1123B. 71 records from Range table from nannofossils in ODP Hole 199-1215A. 1298 records from Planktic foraminifera abundance of Hole 23-219. 347 records from Planktic foraminifera abundance of Hole 21-209. 258 records from Planktic foraminifera abundance of Hole 40-364. 186 records from Planktic foraminifera abundance of Hole 94-610. 222 records from Range table from planktonic foraminifers in ODP Hole 145-887A. 9371 records from Range table from planktonic foraminifers in ODP Hole 152-918D. 4732 records from Range table from planktonic foraminifers in ODP Hole 164-997A. 387 records from Range table from planktonic foraminifers in ODP Hole 182-1134A. 611 records from Range table from benthic foraminifers in ODP Hole 172-1056C. 57 records from Range table from benthic foraminifers in ODP Hole 139-855B. 38 records from Microfossil abundance of Hole 21-206C. 60 records from Phytoplankton abundance in surface water in October 1996, Chimbote, Peru. 6219 records from Specimens of G. Fenoul Herbarium (FEN). 3538 records from NHT_flora. 3027 records from Fungi Collection in BCRC. 236754 records from Countryside Council for Wales - Welsh Invertebrate Database (WID). 767 records from (Figure 8c) Distribution of Cretaceous planktonic foraminifers, calpellionids, and associated organisms from DSDP Hole 77-536. 1416 records from (Table 3) Relative abundances of stratigraphically useful planktonic foraminifers from ODP Hole 167-1012A sediments. 51 records from Colección de Aráceas del Jardín Botánico San Jorge. 2 records from Benthic foraminifera abundance of Hole 42-376. 1769 records from Distribution of benthic foraminifera in DSDP Hole 24-238 in the Central Indian Ocean (Appendix A). 156 records from Colecciones Zoológicas de la Universidad de León, Colección de Malacostráceos. 607 records from King penguin census data, Gadget Gully, Macquarie Island (1993-2008). 319 records from Succession of benthic hard-bottom communities abundance at station Errina2012_MDD4. 210003 records from UMMZ Birds Collection. 1851 records from (Figure 2) Foraminifera in lower to middle Albian sediments of DSDP Hole 80-549. 2443 records from Cnidaria MZS. 468 records from Collection Diptera - SMF. 135 records from Collection Pisces - KAUMM. 3082 records from dec2011. 39 records from Colección de Urocordados. 69 records from Schulgarten mit Klasse 8a (Essen). 51 records from (Table III) Abundance of crustacea orders during RSS James Clark Ross cruise JR144. 571 records from (Appendix A2) Relative abundances of benthic foraminifera and stable carbon isotope ratios of Nuttallides truempyi at the Paleocene-Eocene thermal maximum in ODP Hole 198-1210B in the central Pacific. 102 records from Waldwandel in Monschau-Mützenich-Boverei. 233 records from Briòfits d'Andorra. 1 records from Nothrus sinuatus. 273002 records from Royal Netherlands Institute for Sea Research (NIOZ) - Kom Fyke Mokbaai. 1 records from Orthoptera - SMF. 1 records from On the Chilopoda from Turkey. 350 records from (Table 1) Distribution of Cretaceous redeposited benthic foraminifers at DSDP Hole 89-585. 171765 records from Tromsø Museum, Vascular plants. 164 records from EcoRecord - Reptile records held by EcoRecord for the Birmingham and the Black Country area collated prior to March 2013. 2 records from (Table 3) Late Maastrichtian calcareous nannofossils in ODP Hole 198-1212B. 2046 records from (Table T3) Benthic foraminfera stratigraphy of ODP Hole 199-1221C sediments. 227 records from Countryside Council for Wales - Bat Records - Montgomeryshire. 44 records from (Table 1) Sulphur chemistry of ODP Site 206-1256 volcanic section. 416 records from (Table 3) Benthic foraminiferal genera in DSDP Core 95-612-21-5 and 95-612-21-6. 4 records from Arthropoden aus südostalpinen Höhlen.. 192 records from (Table 2) Relative abundance of selceted benthic foraminifera taxa of DSDP Hole 93-605. 4 records from Pollen analysis of sediment profile HAE10 from Haemelsee. 17 records from MVZ Herp Observations (Arctos). 2 records from Abundance of benthos infauna at station GIK23024-1. 288 records from (Table 1) Abundance of Pleistocene dinoflagellate cysts in ODP Site 133-820. 5 records from Pollen profile RAC20, Lake Racou, France. 3034 records from (Table 2) Occurrence of Late Cretaceous foraminifers and radiolarians in ODP Hole 130-807C. 1391 records from Open Mosaic Habitat Survey Group - Plants recorded during Open Mosaic Habitat survey in England and Wales (2012). 934 records from Nottinghamshire Biological and Geological Records Centre - Nottinghamshire Biodiversity Action Group Japanese Knotweed Survey. 1524 records from (Appendix A2) Planktonic foraminifera and microfossil occurence in ODP Hole 130-806B. 5426 records from Collection Francaise de Bacteries Phytopathogenes. 5344 records from Highland Biological Recording Group - HBRG Other Invertebrates Dataset. 1968 records from Managing open habitats for species conservation: the role of wild ungulate grazing, small-scale disturbances, and scale - Pinus sylvestris pioneer forest. 1 records from A new species of Cottunculus (Teleostei: Psychrolutidae) from the Mid Atlantic Ridge.. 38200 records from Herbario Universidad de Antioquia (HUA). 68 records from Late Pleistocene planktonic foraminifera of Hole 302-M0004C (Addendum 1). 6 records from Total meiobenthos abundance from the Crimea shelf, Black Sea, area I. 1914 records from Macrophytes_CLF. 15 records from Die geheimnisvolle Welt der Spinnen. 29 records from Insekten. 105 records from BIRDRACE coesfelder_vogelkundler. 294 records from Distribution of calcareous foraminifers in sediment core Well 6407/9-3. 83 records from Foraminifera species abundances from tow TT011_7-MOC66. 59 records from Microzooplankton (larger protists and small copepods) abundance measured on concentrated water bottle samples at station PS65/424-22. 15 records from (Table 1) Mean body mass, flipper length, oxidative balance indices and telomere length of king penguin chicks (Aptenodytes patagonicus) at the beginning of the post-winter growth. 25486 records from Biological Records Centre - Opiliones (Harvestman) Dataset. 66679 records from University of Vienna, Institute for Botany - Herbarium WU. 152 records from Assemblage of total living benthic foraminifera in sediment core SO118_MC-35. 316 records from (Appendix 6) Benthic foraminifera at termination II in sediment core GIK23068-3 in the Norwegian Sea. 1070 records from (Table 1) Distribution of agglutinated benthic foraminifera in lower Cretaceous sediments of DSDP Hole 27-263 in the Cuvier Abysaal Plaine, Indian Ocean. 54 records from Total foraminifera counts from M35/1_MSN1057. 6 records from Microzooplankton abundance and biomass at station NBP97-08-36-1. 116 records from Phytoplankton abundance and species composition in the Sicily Channel in October 1991. 4 records from Nannofossil abundance of Hole 4-31. 1500 records from Amphibian and Reptilian (ENHM-AR). 755 records from Helgeland Museum, Syrphidae. 544361 records from BioFokus. 28 records from Hecke - Klassen 2 a und 2 b VS Tussenhausen. 170 records from Bodenseeufer Radolfzell. 23 records from Assemblage of living benthic foraminifera in sediment core SO129_MC-03, >125 µm fraction. 421 records from Benthic foraminiferal assamblage in the >125 micron fraction of sediment core GIK17728-1 (Table 7). 53 records from Plasm bearing foraminifera counts from M35/1_MSN1058. 58 records from Plasm bearing foraminifera counts of multinet M21/2_MSN651. 27 records from Planktic foraminifer Globorotalia menardii counts on sediment core GeoB5121-1. 60 records from Sedimentological investigation on core V25-76. 125 records from Planktic foraminifera counts at CTD station PS55/082-1. 4 records from Nannofossil abundance of Hole 10-89. 23 records from New species of the plesiomorphic genus Nixonia Masner (Hymenoptera: Platygastroidea, Platygastridae) from South Africa.. 191 records from Chinese species of egg-parasitoids of the genera Oxyscelio Kieffer, Heptascelio Kieffer and Platyscelio Kieffer (Hymenoptera: Platygastridae s. l., Scelioninae). 3 records from Beitrage zur Kenntniss paläarctischer Myriopoden. XV. Aufsatz: Lithobiiden aus Bosnien, Herzogovina und Dalmatien. 1025 records from (Appendix 2) Absolute abundance of nannofossils in ODP Hole 183-1135A. 35 records from Aves Argentinas / Asociación Ornitológica del Plata - Colección de registros observacionales de aves silvestres argentinas - Lista Narosky: familia Rhinocryptidae. 6541 records from Likona Invertebrates. 618 records from RSPB - Scottish Crossbill National Survey in the UK in 2008 (SCARABBS). 164 records from John Muir Trust - Species Records for John Muir Trust Properties Nevis, Sandwood, Quinag and Schiehallion 2010.. 49637 records from Monitoring data from the federal state Hesse (Germany). 54244 records from TNHC Ichthyology Collection. 114 records from Birdrace-Finkenspötter-München. 258 records from BIRDRACE Raumpatrouille Oriolus. 77 records from Faunal assemblage of sediment core GS7603-12. 10 records from (Table C) Fauna associated with Bathymodiolus azoricus mussel beds within the Rainbow hydrothermal field, Mid-Atlantic Ridge. 35 records from Neoniphon pencei, a new species of holocentrid (Teleostei: Beryciformes) from Rarotonga, Cook Islands. 1808 records from University of Amsterdam (NL) - Páramo vegetation research, Ecuador.. 59799 records from Plant Specimen from Herbarium (HIB) in China, Wuhan Botanical Garden, Chinese Academy of Sciences. 9 records from Kryptopterus platypogon, a new silurid catfish (Teleostei: Siluridae) from Borneo.. 121 records from (Table 2) Relative contents of planktonic foraminifera in bottom sediments from the Ashadze-1 Hydrothermal Field. 162 records from Siegen/ Gymnasium Am Löhrtor. 151 records from Isarufer. 40 records from Flächennaturdenkmal Grubditz. 101 records from Steinbruch Kronungen. 11 records from Umgebung Jugendherberge Clausthal, Klasse 8d. 33 records from Benthic foraminiferal assemblage (Rose Bengal stained) in MUC OB10-K, turbidite sequence 3. 57 records from Benthic foraminiferal assemblage (Rose Bengal stained) in MUC SC2-L, size fraction 63-150 µm. 140 records from Assemblage of living benthic foraminifera in sediment core GeoB1720-3. 124 records from Total foraminifera counts of multinet M21/1_MSN620. 89874 records from ecoscope_observation_database. 12 records from Phytoplankton abundance in the wadden sea off List, Sylt, North Sea in 1996. 541 records from (Table T6) Biostratigraphy of important benthic foraminifer taxa in sediments cored in Ratekau, Schleswig-Holstein. 2754 records from (Table 7) Benthic foraminifera in middle-late Miocene sediments of DSDP Site 90-590. 2432 records from RSPB - Black Grouse Recovery Project Annual Survey in Argyll & Bute 2002-2009 (RSPB/SNH/FCS/Scottish Power). 94 records from Plasm bearing foraminifera counts from multinet SO119_MSN1284. 9 records from (Table B) Abundance of benthic fauna associated with shrimp swarms at hydrothermal fields on the Mid-Atlantic Ridge. 40 records from Stable carbon and oxygen isotope ratios of calcareous dinoflagellate cysts and planktic foraminifera from the Campanian/Maastrichtian section of ODP Hole 113-690C in the Weddell Sea (Table 1). 25 records from Phytoplankton abundance at station Sechin_2003-12-28_2, Casma, Peru. 1395 records from Alterra (NL) - Microarthropods inventory in grasslands in the province of Friesland. 11 records from Nannofossil abundance of Hole 3-15. 14 records from Nannofossil abundance of Hole 7-64. 48 records from Assemblage of living benthic foraminifera in sediment profile GeoB4901-6. 94 records from Total foraminifera counts from M35/1_MSN1074. 148 records from Total foraminifera counts of multinet M21/2_MSN643. 133 records from Abundance of planktic foraminifera at CTD station PS55/018. 1998 records from Institut Botanic de Barcelona, BC-Lichenotheca. 3 records from Sarcodine counts and carbon biomass at station TT011_1-CTD4. 938 records from Assemblage of dinoflagellate cysts analysed in sediment core SO78-175-1. 142 records from Phytoplankton abundance at station CD47_1206C#7. 10 records from (Table 2) Abundance of benthic foraminifers of sediment core PS2159-3. 446 records from Bayerische Donau - Blindheim Donaubrücke. 206 records from Total foraminifera counts from multinet M31/3_MSN908. 104 records from Plasm bearing foraminifera counts of multinet M21/2_MSN638. 4 records from Microzooplankton abundance and biomass at station TT050_26-17. 11 records from Revalidation of Pterinopelma Pocock 1901 with description of a new species and the female of Pterinopelma vitiosum (Keyserling 1891) (Araneae: Theraphosidae: Theraphosinae). 51 records from Microzooplankton abundance measured on water bottle samples at station PS65/545-1. 37 records from Pollen profile from Arrington Marsh. 43 records from (Table 5) Distribution of calcareous nannofossils in DSDP Holes 92-600C and 92-601. 4 records from Distribution of Quinqueloculina sp. in sediment core 12930-065. 287 records from (Table 3) Distribution of planktonic foraminifera in the smaller size fraction of ODP Hole 120-749B. 137 records from Abundance of planktic foraminifera at CTD station M39/4_352CTD-11. 76 records from Coccolith counts of multinet SO119_MSN1288. 15 records from Benthic macrofauna abundance of sediment core 13200-051. 17 records from Benthic macrofauna abundance of sediment core 13200-073. 5 records from Penguins of Antarctica. 20 records from Molluscs in surface sediments off Sylt collected during Heincke cruise HE255. 190257 records from Ontario Breeding Bird Atlas 2001-2005. 313162 records from Observational database of Icelandic plants. 1901 records from AAD Benthic Sampling Database. 14473 records from Entomology at ZMUC, Natural History Musem of Denmark. 52 records from Plasm bearing foraminifera counts of multinet PO247/2_MSN1382. 1 records from Planktic foraminifera counts of multinet M21/5_MSN728. 4 records from Planktic foraminifera counts of multinet PS31/054. 9 records from (Fig. 3) Pollen analysis of the Bosque de Avicennia core. 1 records from Microzooplankton abundance and biomass at station TT050_25-4. 24 records from Abundance and carbon biomass of phytoplankton at station TT007_8-CTD102. 18 records from Abundance, biovolume and biomass of heterotrophic dinoflagellates at station TT007_7-CTD82. 32 records from Phytoplankton abundance at station Rigel_5_2005-05 in May 2005, Chipana, Chile. 11 records from Phytoplankton abundance at station Sechin_2003-08-27_2, Casma, Peru. 51 records from Microzooplankton abundance measured on water bottle samples at station PS65/522-1. 150 records from Psocodea (Mallophaga) collection of National Museum of Nature and Science. 27 records from Meiofauna abundances at the Arctic Håkon Mosby Mud Volcano (HMMV) of sediment core PS64/395-1. 4 records from Abundance of radiolaria at station UT99-19-2. 288 records from Size of planktic foraminifera at CTD station M39/4_402CTD-55. 22 records from Abundance and carbon biomass of phytoplankton at station TT007_15-CTD162. 6 records from Nano and microzooplankton abundance and biomass at station NBP96-04A-14-13. 6 records from Phytoplankton abundance in surface water in 2005, Ancon, Peru. 48 records from Artenerfassung für Jedermann in der Grundschule Kirchboitzen. 29 records from Nannofossil abundance of Hole 13-132. 19 records from Meiofauna abundance in sediment core 13077-060. 57 records from Kindervilla Aussengelände/ Hiltroper Park. 109 records from (Table 4) Meiofauna abundance in surface sediments of Cape Fear. 176 records from (Table 1) Distribution of main species of planktonic foraminifers in Core AMK21-2168, Woodlark Basin. 84 records from (Appendix B) Calcareous benthic foraminifers in ODP Hole 123-765C. 96 records from (Table 1) Distribution of calcareous nannofossils in ODP Hole 113-689B. 9271 records from APIS - Antarctic Pack Ice Seals 1994-1999, plus historical data from the 1980's. 16489 records from AIMS - GBR Nearshore Coral Diversity (OBIS Australia). 19063 records from Mammal specimens. 321 records from Calcareous dionoflagellate cysts from surface sediments. 1 records from Microzooplankton abundance and biomass at station TT054_24-22. 24 records from Abundance, biovolume and biomass of heterotrophic dinoflagellates at station TT012_5-CTD85. 18 records from Abundance of non-diatom phytoplankton measured on water bottle samples at station PS58/048-3. 24 records from (Fig. 5c) Limacina dissolution index of sediment core GeoB2207-2. 6 records from Nannofossil abundance of Hole 1-7. 19 records from Nannofossil abundance of Hole 24-233. 24 records from Nannofossil abundance of Hole 11-106. 9660 records from (Table 3) Ranges of upper Eocene Holocene planktonic foraminifera in ODP Hole 119-744A. 104 records from Schulwald Sprendlingen. 2392 records from Benthos counted on dredged samples during Valdivia cruise VA44. 78 records from Aktion - Friedensburg Oberschule. 332 records from 6. Tag der Artenvielfalt Hockenheim Thema: Wald 12.-14.6.2009. 1 records from FTEA. 18 records from Cyanobacteria, phototrophic and heterotrophic pico-nanoplankton at station TT012_5-CTD85. 47 records from Nannofossil abundance of Hole 64-479. 24 records from Ostracoda abundance of Hole 42-371. 4 records from Ostracoda abundance of Hole 32-305. 8 records from Little known Orphninae (Coleoptera, Scarabaeidae) collected by the Madagascan expeditions of the California Academy of Sciences. 4 records from Estimated plankton abundance at station PS63/064-6. 102 records from Planktic foraminifera counts of sediment core RC11-145. 14017 records from Museu de Ciències Naturals de Barcelona: MCNB-Art. 1212 records from RMT Trawl catch from the 1990/91 V6 AAMBER2 voyage. 76 records from Nannofossil abundance of Hole 58-445. 53 records from Planktic foraminifera counts of sediment core ELT48.027-PC. 63 records from Planktic foraminifera counts of sediment core V19-21. 1440 records from (Figure 6) Range chart of selected dinocysts and acritarchs of ODP Hole 104-642C. 52 records from (Table 2) Abundance of total planktonic foraminifera and Neogloboquadrina pachyderma in sediment core KNO5103-0029GGC. 47 records from Pollen analysis of sediment core T89-16-PC. 2008 records from Análisis de la heterogeneidad ambiental y conectividad de las áreas naturales del sur del Valle de México_2. 55 records from Niveles y patrones de variación genética del género Abies en México. 384824 records from Herbarium, Botanical Museum, University of Oulu, Finland (OULU). 7966 records from MfN - Phasmid Collection. 311876 records from British Lichen Society - BLS Lichen Database: Scotland. 20945 records from CeDoc de Biodiversitat Vegetal: BCN-Cormophyta. 5224 records from Insect Specimens of Omogo Mountain Museum. 46 records from Nannofossil abundance of Hole 26-254. 15 records from Diatom abundance measured on water bottle samples at station PS58/090-4. 10 records from Abundance of empty diatom frustules measured on water bottle samples at station PS58/088-4. 10 records from Benthic macrofauna abundance of sediment core 12930-059. 11 records from Benthic macrofauna abundance of sediment core 13200-017. 898 records from Planktic foraminifera counts of sediment core V18-357. 153 records from Dinoflagellate cysts from sediment core PS2471-1. 102 records from (Table 3) Distribution of silicoflagellates, actiniscidians, and ebridians in selected samples from ODP Hole 112-685A. 76 records from (Table 1) Counts and concentrations of pollen, spores and dinoflagellate cysts in sediment core MD01-2378. 51 records from (Table 8) Percent distribution of calcareous nannofossils at ODP Hole 125-781A. 13 records from (Table 3) Distribution of some benthic foraminifera in ODP Hole 108-659A. 52 records from Crustacea in surface sediments off Sylt collected during Heincke cruise HE255. 11 records from (Table 2d) Nannofossil distribution chart of petroleum well Great-Eastern-1. 211 records from UAM Mammal Observations (Arctos). 310 records from Umgebung der Gesamtschule Hamburg-Winterhude. 98 records from (Figure 6k and 6l) Nannofossil accumulation rate and absolute abundances of coccoliths from ODP Site 1233. 991 records from Foraminifera abundance of Hole 64-481A. 6 records from Range table from planktonic foraminifers in ODP Hole 171-1049B. 1218 records from Collection Oligochaeta - ZIM Hamburg. 836 records from (Figure 4) Stratigraphic ranges of selected planktonic foraminifers at ODP Hole 101-626D. 228 records from Biodiversidad acuática del río Amacuzac, Morelos, México. Plantas vasculares. 116 records from (Table 2) Dinocyst specimens per slide and relatice abundances in each sample of ODP Hole 120-748C. 2980 records from Museo Nacional de Ciencias Naturales, Colección de Aves: MNCN-Ornit. 15016 records from iziko South African Museum - Fish Collection (AfrOBIS). 195 records from (Table 1) Planktonic foraminifera preservation indexes of ODP Hole 130-805C. 332 records from (Appendix B) Benthic foraminifera in DSDP Site 89-586 sediments. 22 records from Geophagus abalios, G. dicrozoster and G. winemilleri (Perciformes: Cichlidae), three new species from Venezuela.. 434 records from Distribution chart of Holocene benthic foraminifera in the Izu-Bonin Arc (Table 2). 31 records from Pollen record of sediment core Bokanjacko Blato 2. 1344 records from Florística y biogeografía de algunos bosques mesófilos de la Huasteca Hidalguense: Fase 3 (Chapulhuacán y Pisaflores). 1011 records from Biodiversidad fitoplanctónica de cenotes: Patrones espaciales y temporales. 280 records from (Table 3) Distribution of Neogene planktonic foraminifers in sediments of ODP Hole 115-705A. 6811 records from Collection Collembola - SMNG. 1237 records from Distribution of nematodes in Patagonia Argentina coast (OBIS South America, SOUTHERN OCEAN SUB-NODE). 21348 records from Phytopathogenic Fungi Observed by Hans and Hanna Doppelbaur. 2532 records from Visual Plants (144.41.33.158) - Herbarium specimen from the Estacion Scientifica San Francisco, Southern Ecuador. 31 records from (Table 5) Distribution of calcareous nannoplankton in selected samples of ODP Hole 112-682A, Part II. 356 records from (Table T2) Calcareous nannofossil stratigraphy in ODP Hole 186-1151C sediments. 497 records from Inventario herpetofaunístico del valle semiárido de Tehuacán-Cuicatlán (continuación). 8784 records from Bryopytes specimens of Akita Prefectural Museum. 62324 records from Herbarium Specimens of Museum of Nature and Human Activities, Hyogo Pref., Japan. 576 records from (Table 16) Ranges of benthic foraminifers through the Neogene in ODP Hole 115-710A. 11700 records from (Figure 4) Distribution of benthic foraminifers in the Upper Cretaceous of DSDP Hole 71-511. 367092 records from HMAP-History pf Marine Animal Populations (CoML). 2095 records from The SERTC Invertebrate Database: Invertebrates of the southeastern United States. 97951 records from Database Schema for UC Davis [Herbarium Labels]. 21 records from Pollen data of trap CB2. 1473 records from (Appendix 2, Part 1) Distribution of Eocene to Recent benthic foraminifera in ODP Site 113-689. 478 records from Parásitos de peces nativos de cenotes de la Península de Yucatán, un ecosistema único en México. 5 records from Bryophyte Collection of Shizuoka Prefecture Museum of Natural History. 31835 records from Tartu University, palaeontology collections. 26 records from Microplankton abundance at Station MARCH-1998-GN36199804610MSB03 in the euphotic zone of the Aegean Sea in March 1998. Part 3 - coccolithophores and other groups. 90 records from Quaternary radiolarians from offshore eastern New Zealand, ODP Leg 181, Site 1123, relative abundances. 121 records from Total foraminifera counts from multinet M31/2_MSN893. 1768 records from (Appendix A4) Relative abundances of planktonic foraminifera of sediment core GeoB1706-2. 6 records from Sediment properties of core PLG93_BCORE1. 228 records from Occurrence of mammalia relicts at site Grotte Scladina. 570 records from Planktic foraminifera abundance of Hole 94-606. 63 records from Range table from planktonic foraminifers in ODP Hole 167-1015A. 6 records from Collection Tunicata - ZIM Hamburg. 29084 records from Vascular plants of south-central China. 2760 records from RMT Trawl catch from the 1995/96 V4 BROKE voyage. 1353 records from Relative abundance of planktic foraminifera in the 120 kyr time slice reconstruction of sediment core RC12-294. 171 records from Foraminifera abundance of sediment core C1960.201. 5 records from Analyses of the recent components of sediment core PS1216-1. 3 records from Analyses of the recent components of sediment core PS1403-1. 2197 records from Benthic foraminifera distribution of sediment core BP00-07/05. 149 records from Trockenhang Greinhartsberg Edelfingen. 494 records from Biologische Station im Kreis Wesel. 15 records from Phytoplankton abundance in surface water during Akademik Vernadsky cruise AV22. 1322 records from (Table 3) Percentages of planktonic foraminiferal species and varieties from the sediment surface samples from the South China Sea. 5 records from Analyses of the recent components in the sand fraction of sediment core PS1016-1. 177 records from Rund um den Eichwald,Schulhof Friedrich Fröbel Gymnasium- Bad Blankenburg. 651 records from Range table from planktonic foraminifers in ODP Hole 155-940A. 44 records from Royal Horticultural Society - Pittosporum sucker (Trioza vitreoradiata) records acquired by the Royal Horticultural Society . 3 records from Range table from benthic foraminifers in ODP Hole 178-1095A. 38 records from (Appendix D) Stratigraphic occurrence of radiolarian special and species groups in sediments of ODP Hole 199-1220A. 1236 records from Universidad de Oviedo. Departamento de Biología de Organismos y Sistemas: FCO-Algae. 2 records from Abundance of benthos infauna at station PO128/2_281. 10189 records from Royal Museum of Central Africa - Metafro-Infosys - Xylarium. 822 records from Isotope tracer experiment: nematode abundance. 157292 records from Hertfordshire Natural History Society Flora Group - Hertfordshire Flora Survey Records 1987-2005. 19 records from (Table 4) Abundance of Pulleniatina obliquiloculata in sediment core ERDC-139BX. 179 records from Reconstruction of surface water temperature of sediment core GIK12379-1, Cape Barbas, North-West Africa (Appendix Tab. 4). 47 records from Spandau HBO. 28 records from Range table from planktonic foraminifers in ODP Hole 151-910D. 1 records from Range table from planktonic foraminifers in ODP Hole 178-1102C. 102 records from Range table from benthic foraminifers in ODP Hole 139-858A. 331 records from Relative abundance of dead benthic foraminifera in East Atlantic surface sediments off Senegal and Gambia (Table 2). 3207 records from UAFMC Herps. 3 records from Revision der Ceratozetidae, 3. Ceratozetes laticuspidatus n. sp. (Arach., Acari, Oribatei). 5053399 records from Southern African Bird Atlas Project. 15934 records from Mamíferos de la colección del Instituto Alexander von Humboldt. 479 records from (Table 3) Benthic foraminiferal distribution at ODP Site 127-797. 181 records from Total foraminifera counts from multinet M31/3_MSN914. 1505 records from Relative abundance of planktonic foraminifera in Pliocene and Pleistocene sediments of DSDP Hole 32-310 from Hess Rise, Central North Pacific (Table II). 96 records from Alte Ziegelei, Lehmgrube (Mainz-Bretzenheim). 12 records from Microplankton abundance in the euphotic zone of the Aegean Sea at Station JUNE-1998-IR64. 204 records from Range table from benthic foraminifers in ODP Hole 171-1051A. 8 records from Range table from dinoflagellates, acritarchs and prasinophytes in ODP Hole 189-1171A. 287 records from Relative abundance of live (Rose Bengal stained) benthic foraminifera in the large size fraction of surface sediment off NW Africa (Table 5). 413272 records from DATAVES. 12 records from Caracterización de la Íctiofauna presente en la laguna Concepción, Bocana del río Saija (Cauca), sitio sagrado de las comunidades Indígenas de OZBESCAC. 25 records from Description of three new species of the genus Chromaphyosemion Radda, 1971 (Cyprinodontiformes: Nothobranchiidae) from the coastal plains of Cameroon with a preliminary review of the Chromaphyosemion splendopleure complex.. 488 records from Range table from benthic foraminifers in ODP Hole 172-1055C. 144 records from (Table 4) Composition of turbidite and background samples at ODP Site 166-1007. 129635 records from Marine Biological Association - Marine survey data (Professional) held by MarLIN. . 14549 records from Alterra (NL) - Comparison of entomofauna in four different habitats. 31020 records from National Museum of Natural Science. 1025 records from Irish Marine Turtle Database. 26 records from Description of a new cyprinid species, Labeo meroensis n. sp. (Teleostei: Cyprinidae), from the River Nile.. 99 records from VFD-BW, Albvorland: Pferdeweiden Ofterdingen. 297 records from Microplankton abundance at Station SEPT-1997-GN36199704605MSB01 in the euphotic zone of the Aegean Sea in September 1997. Part 2 - dinoflagellates. 12 records from Microplankton abundance at Station SEPT-1997-GN36199704606MNB03 in the euphotic zone of the Aegean Sea in September 1997. Part 3 - coccolithophores and other groups. 6 records from Microplankton abundance at Station SEPT-1997-GN36199704606MNB05 in the euphotic zone of the Aegean Sea in September 1997. Part 3 - coccolithophores and other groups. 100 records from Occurrence of mammalia relicts at site Biedermann. 654 records from Benthic foraminifera abundance of Hole 56-435. 528 records from Range table from planktonic foraminifers in ODP Hole 141-860B. 40 records from Range table from planktonic foraminifers in ODP Hole 151-908A. 24 records from Range table from planktonic foraminifers in ODP Hole 170-1039A. 20 records from Range table from planktonic foraminifers in ODP Hole 175-1078C. 108 records from Phytoplankton abundance off Guañape bay in Juli 2003, Peru. 28 records from Range table from planktonic foraminifers in ODP Hole 178-1096B. 76 records from Live (Rose Bengal stained) benthic foraminifera from surface sediments of the Indian and Pakistan continental margin (Table 1). 1088 records from Relativ abundances of total dead fauna of benthic foraminifera in surface sediments (Table C1.2). 1 records from Oppia glaucina. 2467 records from Coleccion Herpetologica Reptiles LJAMM-CNP. 319 records from Field Study Group of the Dutch Mammal Society (NL) - 2010 - Mammal Survey Patvinsuo National Park, northern Karelia, Finland. 6 records from On the ants (Hymenoptera: Formicidae) of the Philippine Islands: V. The genus Odontomachus Latreille, 1804.. 7617 records from Fundacin Miguel Lillo - Coleccin Fanerogmica. 244 records from Scottish Natural Heritage - The ecology of Najas flexilis (Slender naiad) . 8136 records from Zoological Museum Amsterdam, University of Amsterdam (NL) - Coelenterata. 1172 records from (Table T1) Benthic foraminfera stratigraphy of ODP Hole 199-1215A sediments. 17802 records from The Bat Conservation Trust - Colony Count Survey. 3 records from Beiträge zur Kenntnis der Oribatiden (Acari) Europas I. Zwei neue Arten der Gattung Suctobelba Paoli aus der Oberlausitz (DDR): Suctobelba scalpellata n. sp. und Suctobelba secta n. sp.. 1 records from Nothrus bicarinatus. 154 records from Specimens from India at the NTNU University Museum in Trondheim. 1550 records from Species counts of benthic foraminifera of sediment core BOFS14K. 249 records from Silbertor + Wasserbachtal (Rutesheim / Renningen). 14 records from Range table from planktonic foraminifers in ODP Hole 178-1101A. 311 records from Range table from planktonic foraminifers in ODP Hole 192-1186A. 1680 records from Distribution of reworked planktic foraminifera in Neogene sediments of core CLINO from the Great Bahama Bank (Table 1). 36 records from Dinoflagellate abundance of Hole 40-365. 645 records from Phytoplankton abundance in surface water in March 1997, Ilo, Peru. 489 records from ANTXXIII-8 Birds and Mammals (SCAR-MarBIN: Antarctic OBIS). 118 records from Siliceous microfossil occurrence, Site 177-1091. 194 records from (Table S2) Coccolithophora in sapropel S1 of ODP Hole 160-964B, filtering preparation. 4888 records from (Table 1) Distribution and relative abundance of mid-Cretaceous planktonic foraminifers at DSDP Hole 79-545. 18959 records from Herbarium Specimens of Bonin and Ryukyu Islands. 125051 records from Natural History Museum Rotterdam (NL) - Insecta collection. 790 records from Relative abundance of dead benthic foraminifera of sediment core M5/2_100MC. 3536 records from Live (Rose Bengal stained) benthic foraminifera of surface sediments of the Persian Gulf (Table 1). 534 records from Leopard Seal census, Heard Island 1987/88. 1400 records from Bird specimen detabase of Kanagawa Prefectural Museum of Natural History. 91416 records from Collection Mammalia SMF. 2015 records from (Appendix B) Benthic foraminifera extinction group species in combined DSDP Hole 33-317B and sediment core KR9912-PC4. 371 records from Fossil occurrence of planktonic foraminifera from IODP Hole 315-C0001H. 13040 records from CUMV Reptile Collection (Arctos). 23341 records from Fundación Miguel Lillo - Colección Herpetológica. 6109 records from UNR Herpetology. 9717 records from The Orchid Atlas of Western Australia. 1 records from Nothrus posticus. 1 records from Über einige von Jaroslav Storkán in Bulgarien gesammelte Chilopoden. 38543 records from Record, the Biodiversity Information System for Cheshire, Halton, Warrington and the Wirral - RECORD other mammal data up to current day. 25 records from Countryside Council for Wales - Freshwater Gwyniad Survey Data. 8 records from Content of G. menardii in sediment core V25-69. 11 records from Microzooplankton abundance and biomass at station TT043_28-1. 16 records from Phytoplankton abundance at station Rigel_1_2005-02 in Febraury 2005, Chipana, Chile. 14 records from Phytoplankton abundance at station Sechin_2003-09-18_1, Casma, Peru. 454 records from Colección de Entomología - Hymenoptera - Aculeata. 1 records from Oribates fusifer. 3709 records from Naturalis National Natural History Museum (NL) – Cnidaria and Porifera fossils. 4 records from Zwei neue Arten der Oribatiden-Gattung Nanhermannia. 968 records from TTRS Mammals. 1592 records from Aves Argentinas / Asociación Ornitológica del Plata - Colección de registros observacionales de aves silvestres argentinas - Lista Narosky: familia Furnariidae. 1150 records from RSPB - Great Yellow Bumblebee sightings data in the UK, 1990 onwards (RSPB, BBCT, HBRG).. 19451 records from Herbarium of the Department of Natural Forests (Forest Research Institute). 2 records from Nannofossil abundance of Hole 3-20C. 3664 records from Primera caracterización biológica de plantas del proyecto "Incorporación de la Biodiversidad en el sector cafetero en Colombia". 25128 records from Royal Museum of Central Africa - Albertian Rift Butterflies (ENBI wp13). 2 records from Oribatids from Switzerland I. (Acari: Oribatida). (Acarologica Genavensia LXXXI). 215 records from (Table 8) Benthic foraminifera genera assemblage at DSDP Section 80-548A-28. 807 records from National Trust for Scotland - NTS Properties Sensitive Species Records 1800-2013. 58 records from Mamíferos laguna El Tinije. 6 records from Arthropoden aus südostalpinen Höhlen. 39 records from Kryptopterus geminus, a new species of silurid catfish (Teleostei: Siluridae) from mainland Southeast Asia.. 275 records from Dinoflagellate cysts in surface sediment samples of Meteor cruises M20/2, M23/1, M34/1, M34/2, M34/3 and M34/4. 6 records from Microzooplankton abundance and biomass at station TT043_13-1. 1 records from Microzooplankton abundance and biomass at station TT050_13-15. 10 records from Phytoplankton abundance at station Sechin_2003-11-06_1, Casma, Peru. 4 records from Nannofossil abundance of Hole 16-156. 65 records from Revalidation and redescription of Pterocryptis anomala (Herre, 1933), a catfish (Teleostei: Siluridae) from southern China.. 26847 records from Merseyside BioBank - North Merseyside Other Taxa (unverified). 923 records from Colección Plantas Vasculares - Herbario del Departamento de Biología, Bioquímica y Farmacia de la Universidad Nacional del Sur. 100 records from Grenzturm Hohen Neuendorf. 29 records from Brenz (Heidenheim). 1100 records from (Fig. 6) Assemblage of benthic foraminifera in sediment core GeoB6730-1. 267 records from Assemblage of living benthic foraminifera in sediment core GeoB3713-1. 1 records from Pollen analysis of sediment profile KAIX_B from Kaiserwinkel. 195719 records from Colección Herbario Federico Medem Bogotá - FMB. 1329 records from Colección de Invertebrados Cenpat (CNP-INV). 21694 records from arim. 4852611 records from Bird Ringing Centre in Sweden (NRM). 55 records from Towards the conservation of parasitoid wasp species in Canada: Preliminary assessment of Microgastrinae (Hymenoptera: Braconidae). 95 records from Ortelsbruch - Hangmoor bei Morbach. 57 records from Schulgarten Fichteschule. 90 records from Birdrace-Uttenreuther_Spatzenzähler-Erlangen/Höchstadt. 4738 records from (Table 3) Distribution of Miocene planktonic foraminifers in sediments of ODP Hole 138-845A. 57879 records from Albany Museum Grant. 176 records from Abundance of phytoplankton, heterotrophic nanoflagellates and bacteria through the water column at time series station L4 in the Western English Channel in 2010. 37014 records from Ministerio de Medio Ambiente, y Medio Rural y Marino. Dirección General de Medio Natural y Política Forestal. Inventario Nacional de Biodiversidad 2007, Reptiles. 121 records from Owere Fiddel. 143 records from Total foraminifera counts of multinet M21/3_MSN674. 133 records from Planktic foraminifera counts at CTD station PS55/018. 13 records from Phytoplankton abundance at station Casma_2003-03-27_2, Casma, Peru. 1 records from Range table from nannofossils in ODP Hole 139-855C. 349 records from Planktic foraminifera counts of sediment core V20-170. 55 records from "Schule am Inselsee" Güstrow. 303 records from Garten J. Scherrer (Lachen-Speyerdorf). 2330 records from Seaweed (Plantae) Collection of the Seto Marine Biological Laboratory, Kyoto University. 51 records from Schrebergarten Düsseldorf Oberkassel. 721 records from IBF Monitoring of Plant Galls. 82 records from BIRDRACE Die Ziegeneier. 96 records from BIRDRACE OAG Neuwerk. 177 records from BIRDRACE Mehr Seh Team. 76 records from Faunal assemblage of sediment core GS7603-10. 88 records from Total foraminifera counts of multinet SO118_MSN1265. 881 records from Marine Biological Association - DASSH Data Archive Centre expert sighting records. 160 records from Total foraminifera counts of multinet M21/1_MSN607. 134 records from Ostracoda abundance of Hole 48-403. 2 records from Nannofossil abundance of Hole 94-610D. 2 records from Range table from nannofossils in ODP Hole 139-855A. 3 records from Abundance of broken diatom frustules measured on water bottle samples at station PS58/049-3. 115 records from Wismar Bucht coast-watching. 10183 records from Planktic foraminifera counts of sediment core MD95-2040. 110 records from Total foraminifera counts of multinet PO247/2_MSN1375. 143 records from Total foraminifera counts of multinet PO247/2_MSN1386. 77 records from Foraminifera species abundances from tow TT011_9-MOC69. 26 records from Content of coarse fraction and G. menardii in sediment corev V25-42. 2300 records from Botanical Society of the British Isles - Demonstration set of data downloaded from the BSBI threatened plant database. 54402 records from Naturhistorisches Museum Mainz, Feldbeobachtungsdaten Pflanzen. 8 records from Microzooplankton abundance and biomass at station NBP97-08-25-4. 17 records from Phytoplankton abundance at station Sechin_2003-10-22_2, Casma, Peru. 18 records from Phytoplankton abundance during G. M. Dannevig cruise GMD91/10. 4 records from Distribution of meiobenthos in sediment core M19_217-2 of the northeastern Atlantic (Table 1). 4352 records from (Fig. 3) Stratigraphic ranges of Oligocene planktonic foraminifera and identified biozones in DSDP Hole 77-538A. 59 records from Plasm bearing foraminifera counts of multinet PO247/2_MSN1388. 15 records from Phytoplankton abundance at station Rigel_3_2005-04 in April 2005, Chipana, Chile. 11 records from Zoobenthos in surface sediments off Cape Lucul. 10 records from Abundance of radiolaria at station UT99-21-2. 7 records from Abundance of radiolaria at station UT99-22-1. 4 records from Nannofossil abundance of Hole 2-8A. 3 records from Nannofossil abundance of Hole 9-83A. 21 records from Vogelwelt im Europa-Rosarium. 111 records from Total foraminifera counts of multinet M10/2_MSN219. 51 records from Plasm bearing foraminifera counts of multinet M21/5_MSN732. 179 records from Total foraminifera counts of multinet M21/6_MSN768. 20 records from Planktic foraminifer Globorotalia menardii counts on sediment core GeoB5115-1. 11 records from Microzooplankton abundance and biomass at station TT045_17-2. 10 records from Phytoplankton abundance at station Rigel_5_2005-03 in March 2005, Chipana, Chile. 244 records from Phytoplankton abundance during HYDROMET cruise Hydromet90/4. 5 records from Distribution of meiobenthos in sediment core M19_234-2 of the northeastern Atlantic (Table 1). 148 records from Total foraminifera counts of multinet M21/2_MSN638. 117 records from Granulometry and foraminiferal content of sediment core PI-88-AR_P3. 7 records from Microzooplankton abundance and biomass at station NBP97-08-29-1. 25 records from Phytoplankton abundance at station Sechin_2003-11-25_2, Casma, Peru. 17 records from Meiofauna abundances at the Arctic Håkon Mosby Mud Volcano (HMMV) of sediment core PS64/312-1. 30 records from Nannofossil abundance of Hole 29-281. 7 records from Diatom abundance measured on water bottle samples at station PS58/107-5. 13 records from Benthic macrofauna abundance of sediment core 13200-008. 300 records from (Table 2) Occurrence of ostracoda in sediment core PS2200-5. 150 records from (Table 3) Numerical abundances of nannofossil taxa in ODP Hole 126-791A. 451 records from Nannofossil abundance of Hole 15-148. 2 records from Nannofossil abundance of Hole 6-57A. 1039 records from (Table 3) Relative abundances of benthic foraminifera in ODP Site 120-748. 716 records from (Table 3) Benthic foraminiferal assemblage in the late Pliocene interval of Site 162-984. 100 records from Lower Cretaceous vertical distribution of calcareous dinoflagellate cysts in ODP Hole 122-761C. 375 records from (Table 3) Relative abundances of benthic foraminifera in ODP Hole 105-646A. 44 records from (Table F3) Occurrence of some well known benthonic foraminiferal species in samples from DSDP Site 6-49. 168 records from Die Teiche im Britzer Garten. 5 records from Nannofossil abundance of Hole 3-22. 67 records from Nannofossil abundance of Hole 29-278. 28 records from Nannofossil abundance of Hole 1-3. 2 records from Nannofossil abundance of Hole 94-610. 19 records from Nannofossil abundance of Hole 36-329. 12 records from Diatom abundance measured on water bottle samples at station PS58/012-5. 68 records from Matter enrichment of the macrofauna community of MAC station 13200-005. 69 records from Planktic foraminifera counts of sediment core RC17-113. 9067 records from Atlas Nacional de Anélidos Poliquetos de México (ICMyL-DF, UNAM). 909 records from South American Antarctic Marine Biodiversity Literature. 65 records from Cuxhaven Schlosspark, Klasse 5e- Amandus-Abendroth-Gymnasium. 141 records from Echinoderms in surface sediments off Sylt collected during Heincke cruise HE206. 14278 records from (Table 4) Stratigraphic ranges and relative abundances of Paleogene planktonic foraminifers and other selected organisms in ODP Hole 114-700B. 3259 records from Florística de áreas protegidas en el estado de Durango. 6 records from Description of lithologic section units of IODP Hole 325-M0054B. 24 records from Collection Onychophora - SMF. 32466 records from Marine and Coastal Management - Linefish Dataset (Second Semester of 2005) (AfrOBIS). 399 records from CECT Spanish Type Culture Collection(Fungi). 13195 records from Fish Collection of Natural History Museum and Institute, Chiba. 1000 records from Plant Specimens of Taga Town Museum, Shiga Pref., Japan. 9858 records from Universidad de Murcia, Dpto. Biología Vegetal (Botánica), Murcia: MUB-MUSCI. 975 records from Danielsberg (Mölltal, Kärnten). 10424 records from The Lichen Collection at the Botanische Staatssammlung München. 18 records from Meiofauna abundance in sediment core 13200-012. 19 records from Exkursion in der Ehrbachklamm/ an den Erbach. 10049 records from Shellfish (NSMK-MS). 178 records from Polychaetes in surface sediments off Sylt collected during Heincke cruise HE233. 23 records from (Table 1) Distribution of palynomorphs in ODP Hole 123-765C. 1016 records from Diversidad de los coleópteros Scarabaeiodea del estado de Puebla (II). 40 records from Potencial económico de la flora útil de los cafetales de la Sierra Norte de Puebla. 127 records from (Appendix E) Stable carbon and oxygen isotope composition of Globigerinoides sacculifera of ODP Hole 121-758B. 4801101 records from Botanical Society of the British Isles - Vascular Plants Database additions since 2000. 361 records from Stable isotopes and content of foraminifera at Hole 130-805C. 116 records from Census of calcareous nannofossil taxa expressed as percent of total number of individuals counted, ODP Site 120-748. 64 records from (Table 2) Distribution of calcareous nannofossils in ODP Hole 119-738C. 2918 records from Wood-living beetles 2009. 29710 records from The Vascular Plant Collection at the Botanische Staatssammlung München. 1496 records from (Table 4) Distribution of planktonic foraminifers in ODP Hole 108-658A. 20 records from (Table 2) Stratigraphic occurrence of selected diatom species from DSDP Hole 12-112. 27 records from (Table 12) Distribution of calcareous nannoplankton in selected samples of ODP Hole 112-688A. 836 records from (Appendix 1) Late Cretaceous benthic foraminifera of ODP Hole 207-1257A. 11 records from Pollen profile Märchenwald C, Harz, Germany. 139 records from Corvids Literature Database. 6 records from Folklore and Natural History Museum Mammal. 704 records from DSMZ Collection on Plant Cell Cultures. 132 records from Distribution of planktonic foraminifers in ODP Hole 104-642A (Table 2). 2109 records from Helmintos de peces dulceacuícolas de México. 580 records from Herpetofauna de la reserva de la biósfera Valle de Tehuacán-Cuicatlán (etapa final). 1718 records from Inventario nacional de especies vegetales y animales de uso artesanal. 45841 records from Marine and Coastal Management - Linefish Dataset (First Semester of 2004) (AfrOBIS). 1221 records from NBM Unionoids. 6957 records from Botanical Museum, Copenhagen, the Lichen Herbarium. 88509 records from Herbarium Specimens of Museum of Nature and Human Activities, Hyogo Prefecture, Japan. 994 records from Distribution of planktic foraminifera in sediment core GIK23074-1. 66 records from (Appendix A5) Relative abundances of planktonic foraminifera of sediment core GeoB1711-5. 67 records from (Table 5) Percent distribution of calcareous nannofossils at ODP Hole 125-786A. 105 records from (Table 2) Components of turbidite samples of ODP Leg 101 holes. 12 records from Seawater carbonate chemistry and biological processes during experiments with early life stages of the blue mussel Mytilus edulis, 2010. 353 records from (Appendix 4) Stable oxygen isotope record of Globigerina bulloides and abundances of Neogloboquadrina pachyderma and ice-rafted debris in sediment core MD95-2040. 67 records from (Table 2) Distribution of ostracodes in ODP Hole 107-650A. 176 records from Larval fish at Helgoland Roads in 2003. 16 records from A new fungus-growing ant genus, Mycetagroicus gen. nov. with the description of three new species and comments on the monophyly of the Attini (Hymenoptera: Formicidae).. 210 records from Pliocene/Pleistocene benthic foraminiferal abundances from ODP Hole 167-1012B. 978 records from Aves de las reservas de la biosfera de Durango: La Michilía y Mapimí. 111 records from (Table 8) Distribution of Pleistocene to early Pliocene nannofossils in ODP Hole 108-662A. 1644 records from Bohart Museum of Entomology, UCD. 325 records from Planktic foraminifera abundance of Hole 32-305. 230 records from Range table from benthic foraminifera in ODP Hole 199-1220B. 2291 records from (Table 3) Distribution of benthic foraminifera in early Paleogene sediments of DSDP Hole 27-259, Perth Abyssal Plain off Western Australia. 47672 records from Birds (KIDR-BI). 1186 records from Inventarios de Fauna y Flora en Relictos de Bosque en el Enclave Seco del Río Amaime, Valle del Cauca. 78 records from Birdrace-Die_Laufenten-Braunschweig. 234 records from (Table 2) Selected planktonic foraminiferal species and other microfossil data for sedimentcore P69. 4175 records from (Appendix 2, Part 4) Distribution of Maestrichtian to Paleocene benthic foraminifera in ODP Site 113-690. 7311 records from Riqueza y distribución de especies vegetales en la Península de Baja California. 58355 records from IG TUT paleontology. 28 records from (Table 7) Abundance of different Emiliania huxleyi cells in 0-25 m layer (upper mixed and thermocline layers) and in >25 m layer (under the thermocline) at Stations AH-2001-B3 and AH-2001-B3A. 462 records from Antarctic Fur Seal Populations on Heard Island Summer 1987-1988. 5294 records from Planktic foraminifera counts of sediment core PS2644-5. 44 records from Planktic foraminifera assemblage in sediment core GIK23256-1. 63 records from Planktic foraminifera assemblage in sediment core GIK23243-2. 26753 records from Fish collection of the Museum of Nature and Human Activities, Hyogo. 51927 records from ANTARCTIC PLANT DATABASE. 679 records from Inventaire National du Patrimoine Naturel : Programme national espèces végétales de la Directive Habitat. 834 records from Relative abundance of planktic foraminifera in the 120 kyr time slice reconstruction of sediment core A180-073. 1654 records from (Appendix A5) Relative abundances of planktonic foraminifera of sediment core GeoB1711-4. 424 records from Bulk components and planktonic foraminifera of sediment core GeoB3375-1. 5 records from Analyses of the recent components of sediment core PS1016-1. 242 records from (Fig. 3) Age and multiproxy studies of sediment core GeoB7186-3. 238 records from Umgebung der Gesamtschule Winterhude (Hamburg). 515 records from (Table 2) Neogene benthic foraminifers of ODP Hole 120-748B. 61010 records from Fish Collection of Hokkaido University. 7939 records from Botany registration database by Danish botanists. 353 records from Planktic foraminifera distribution of sediment core GIK17940-2. 145 records from Planktic foraminifera abundance of Hole 9-76A. 290 records from Foraminifera abundance of Hole 64-477. 2087 records from Range table from planktonic foraminifers in ODP Hole 144-871A. 14 records from Range table from planktonic foraminifers in ODP Hole 159-962B. 205 records from Range table from benthic foraminifers in ODP Hole 192-1185A. 112 records from Range table from benthic foraminifers in ODP Hole 198-1214A. 876 records from Phytoplankton abundance in surface water in July-August 1996, Ilo, Peru. 8 records from Pollen analysis of sediment profile BUA1 from Buchsee. 85 records from Birdrace-Halsbandschnäpper-Stuttgart. 51 records from Planktic foraminifera assemblage in sediment core GIK23066-2. 1158 records from Bulk components and planktonic foraminifera of sediment core GeoB7139-2. 63364 records from CCAMLR historic KRILL. 207 records from Geo-Tag der Artenvielfalt Süßen Hornwiesen-Grundschule. 153 records from VSN-Wiese. 146 records from Birdrace-Wannacks_Topti(c)ker-Lübeck. 12 records from Abundance of microplankton from bottle APRIL-2000-K3. 132 records from Microplankton abundance at Station SEPT-1997-GN36199704606MNB01 in the euphotic zone of the Aegean Sea in September 1997. Part 2 - dinoflagellates. 20 records from Microplankton abundance in the euphotic zone of the Cretan Sea at Station JULY-1995-D4. 1 records from Planktic foraminifera abundance of Hole 28-274. 172 records from Range table from planktonic foraminifers in ODP Hole 141-863B. 7 records from Range table from planktonic foraminifers in ODP Hole 159-959D. 19 records from Range table from planktonic foraminifers in ODP Hole 181-1119C. 24 records from Range table from benthic foraminifers in ODP Hole 192-1185B. 513 records from Occurrences des observations de la campagne REMMOA Antilles (2008). 199 records from Halberg bei Neumorschen. 16 records from Occurrence of mammalia relicts at site Buchenloch. 399 records from Planktic foraminifera abundance of Hole 14-142. 686 records from Planktic foraminifera abundance of Hole 45-395. 1 records from Dinoflagellates, pollen and spore abundance of Hole 29-281. 127 records from Benthic meiofauna abundance in surface sediment of core PLG93_BCORE6. 1210 records from NPWS Seal Database. 1 records from Nothrus biurus. 1 records from Miriapodi di alcune grotte della Campania. 98 records from BIRDRACE Die Paradiesvögel. 106 records from BIRDRACE Die Göttinger Sozialbrachvögel. 107 records from BIRDRACE Borussia Zippammer. 640 records from CRSN-Lwiro Herbarium, Kahuzi-Biega National Park (CABIN project). 91 records from GEO-Tag mit der NAJU des Landkreises Ahrweiler am Bausenberg. 124 records from Occurrence of mammalia relicts at site Pod hradem. 682 records from Planktic foraminifera abundance of Hole 29-279A. 415 records from Planktic foraminifera abundance of Hole 29-281. 176 records from Planktic foraminifera abundance of Hole 62-463. 18000 records from Molluscan specimen database of Kanagawa Prefectural Museum of Natural History. 5237 records from Universidad de Málaga: MGC-Algae. 32 records from Revision of the genus Sinopoda Jäger, 1999 in Laos with discovery of the first eyeless huntsman spider species (Sparassidae: Heteropodinae). 3 records from Hornmilben (Oribatida) [pages 213 to 260]. 18970 records from Cowan Tetrapod Collection - Birds. 2398 records from Fleas (Siphonaptera) of Ireland. 2008 records from Colección de artrópodos del PNN Gorgona - Museo de Entomología de la Universidad del Valle (MUSENUV). 192 records from (Table 4) Live benthic foraminifera in sediment core SO130-242MC. 439 records from Museu Paraense Emilio Goeldi - Scorpiones Collection. 1 records from Beitrage zur Kenntniss paläarctischer Myriopoden. XV. Aufsatz: Lithobiiden aus Bosnien, Herzogovina und Dalmatien. 158 records from Planktic foraminifera abundance of Hole 16-155. 159 records from Range table from planktonic foraminifers in ODP Hole 180-1109C. 248 records from Range table from benthic foraminifers in ODP Hole 198-1210A. 3 records from Dinoflagellate abundance of Hole 85-572D. 148 records from Abundance of birds in the Lena Delta Region. 217 records from 5.Tag der Artenvielfalt: Thema Stadtbiotope. 3324 records from Crustacea collection of the Finnish Museum of Natural History. 1973 records from Foraminifera abundance of Hole 61-462. 35 records from Aves Argentinas / Asociación Ornitológica del Plata - Conteo anual de chorlos de pastizal en Argentina - Campaña marzo 2007. 52 records from Range table from planktonic foraminifers in ODP Hole 151-913A. 511 records from Range table from dinoflagellates, acritarchs and prasinophytes in ODP Hole 189-1170D. 246 records from Berkel. 1742 records from SCID Database. 465 records from Fish catch from 1996/97 Voyage 2 WASTE (WOCE Antarctic Southern Transect Expedition). 47499 records from Sphaeroceridae Collection. 5 records from Range table from planktonic foraminifers in ODP Hole 172-1059A. 38917 records from Gunma Museum of Natural History, Vascular Plant Specimen. 1 records from Leptothorax athabasca sp. n. (Hymenoptera: Formicidae) from Alberta, Canada, an ant with an apparently restricted range.. 25727 records from Irish National Badger Sett Database. 39615 records from Irish vascular plant data 1999-2009. 90 records from Succession of benthic hard-bottom communities abundance at station Errina2012_IS_solar3. 1 records from Nothrus furcatus. 1159 records from Countryside Council for Wales - Bat Roosts Database - North East Wales. 1 records from Zetes dorsalis. 2 records from (Table 10) Abundance of silicoflagellates and ebridians in selected samples from ODP Hole 138-854B. 5605 records from Distribution of barnacles, bivalves, gastropods, and calcified worm tubes in sediment samples collected between 1995 and 2010 in the San Francisco Bay coastal system. 5202 records from (Table 1) Distribution of benthic foraminifera on sediment core PS2837. 144 records from Whale Observations from the British, Australian and New Zealand Antarctic Research Expedition (BANZARE) voyages 1929-30 and 1930-31. 44 records from Phytoplankton abundance measured on water bottle samples during Jan Mayen cruise JM6. 55 records from (Table S2a) Nannofossil species richness in the Bass River section. 1 records from Die Myriopodenfauna von Albanien und Jugoslavien. 15 records from Chenopodium. 65 records from LSG "Großes Bruch". 36 records from Liether Park 1 (LMS), Klasse 5b. 206 records from Total foraminifera counts from multinet M31/3_MSN907. 55 records from Plasm bearing foraminifera counts of multinet SO118_MSN1265. 34 records from Marine Conservation Society - Palinurus elephas or Crawfish sightings in the UK and Ireland from 1969 to the present time.. 1 records from The ant genus Pseudaphomomyrmex Wheeler, 1920 a junior synonym of Tapinoma Foerster, 1850.. 1252 records from Aquatic Coleoptera Conservation Trust - SNH site condition monitoring of SSSIs for water beetles 2010. 1196 records from Entomological collection of the National Museum. 73 records from Revision of the ant genus Streblognathus (Hymenoptera: Formicidae: Ponerinae).. 16 records from (Table V) Distribution of diatoms in samples from Heidemann Valley trench, Antarctica. 6774 records from Visherintroductie - Reintroduction of the fishes chub, dace, burbot, and brown trout in Flanders, Belgium. 396314 records from British Lichen Society - BLS Lichen Database: English churchyards. 29087 records from Naturalis Biodiversity Center (NL) - Collembola. 144 records from Taxonomy of the South American genus Pachypops Gill 1861 (Teleostei: Perciformes: Sciaenidae), with the description of a new species.. 3 records from Two new South American species of Monomorium Mayr with taxonomic notes on the genus.. 185294 records from Mycology herbarium, Oslo (O). 19723 records from Moss herbarium, UiB. 17520 records from Arthropod collection, Tromsø Museum. 149 records from Museu Paraense Emilio Goeldi - Amblypygi Collection. 3253 records from ISU Birds. 3204 records from Faunal Inventory of Morysin Nature Reserve. 6 records from (Table 1) Abundance of ciliates, dinoflagellates, nauplii and krill at different stations in the Godthabsfjord. 296072 records from Dr Francis Rose Field Notebook Project - Field Notebook Records of Dr Francis Rose 1950's to 1990's. 1 records from Beitrage zur Kenntniss paläarctischer Myriopoden. XV. Aufsatz: Lithobiiden aus Bosnien, Herzogovina und Dalmatien. 334 records from BIRDRACE Cuxland - Schwenke Geo Consult. 259 records from (Table 7) Benthic foraminifera genera assemblage at DSDP Section 80-548A-22. 455 records from (Table T2) Calcareous nannofossil abundance across the Oligocene/Miocene boundary of ODP Hole 189-1168A sediments. 2000 records from Colección Científica de Referencia Zoológica del Chocó- Herpetología. 300 records from (Table 3) Distribution of recurrent benthic foraminifera at DSDP Hole 75-530A, from Coniacian-Santonian to Albian. 2876 records from Naturalis National Natural History Museum (NL) – Mollusca fossils. 1725 records from (Table 1) Planktonic foraminifer stratigraphy in ODP Hole 167-1021C sediments. 2 records from Pantopoda SMF. 16568 records from Inventaire National du Patrimoine Naturel : Données des campagnes de Suivi Aérien de la Mégafaune Marine (SAMM) de France métropolitaine. 205653 records from Inventaire National du Patrimoine Naturel : Oiseaux nicheurs de France. 252125 records from Moths Ireland. 101 records from Naturgrundstück (Eutin). 41 records from Örtzemündung (Stedden). 9871 records from Dumfries and Galloway Environmental Resources Centre - Micro-moths distribution for Dumfries and Galloway. 96 records from Birdrace-Berlin_Sparrows-Uckermark. 106923 records from Naturalis Biodiversity Center (NL) - Lepidoptera. 450 records from Sea surface temperature and salinity reconstructions for sediment core LaPAS-KF02. 16621 records from Crustacea collection of National Museum of Nature and Science. 400 records from Colección Limnológica del Chocó. 7 records from (Table 4) New palynological record of sediments from Odderade. 12 records from Benthic foraminiferal assemblage (Rose Bengal stained) in MUC OB10-K, turbidite sequence 2. 23 records from Plasm bearing foraminifera counts from multinet M32/3_MSN958. 161 records from Total foraminifera counts of multinet M21/3_MSN671. 22 records from Content of coarse fraction and G. menardii in sediment corev V25-47. 15 records from Large protozoa abundance measured on concentrated water bottle samples at station PS58/107-6. 5346 records from Araneidae specimen database of Osaka Museum of Natural History. 1658 records from Aves Argentinas / Asociación Ornitológica del Plata - Conteo anual de chorlos de pastizal en Argentina - Campaña enero 2009. 110 records from Abundance of dead benthic foraminifera in sediment core CD86_08_BC5. 203 records from Size of planktic foraminifera at CTD station M39/4_366CTD-22. 43 records from Diatom assamblage in samples from sediment trap NB6. 3 records from Sarcodine counts and carbon biomass at station TT011_4-CTD46. 22 records from Microzooplankton abundance measured on water bottle samples at station PS65/587-1. 13 records from Distribution of meiobenthos in sediment core M19_238-2 of the northeastern Atlantic (Table 1). 7 records from Nannofossil abundance of Hole 38-336. 14 records from Nannofossil abundance of Hole 94-611A. 85 records from Schulgelände IGS Kaufungen. 48 records from Heider Bergsee (Brühl). 35 records from Scottish Natural Heritage - Information on capercaillie distribution collected during the âProductivity of breeding Capercaillie Tetrao urogallus at sites across their Scottish range 2011â monitoring project.. 192 records from "Schwarzwassertal" bei Pobershau. 46 records from Living benthic foraminifera at station M33/1_MC-19 (CAST), size fraction 63-125 µm. 291 records from Benthic foraminifera counts of sediment core GIK17730-4. 51 records from Plasm bearing foraminifera counts from multinet SO119_MSN1285. 49 records from Total foraminifera counts of multinet M10/2_MSN251. 16087 records from RSPB - Corncrake national surveys - territory centres (SCARABBS). 45006 records from Fungi field notes, Oslo (O). 95 records from Überschwemmungsgebiet der Wied. 72 records from Faunal assemblage of sediment core TR149-35. 184 records from Total foraminifera counts of multinet SO117_MSN1244. 229 records from Total foraminifera counts of multinet SO117_MSN1245. 78 records from Total foraminifera counts of multinet M21/4_MSN695. 67 records from Total foraminifera counts of multinet M21/5_MSN734. 144 records from (Table 8) Planktonic foraminifera species in bottom sediments of Core ML3_198-4GC, North Atlantic. 11 records from Nannofossil abundance of Hole 15-153. 49 records from RSPB - Turtle Dove sightings from research project in East Anglia, 2010. 172 records from Total foraminifera counts of multinet SO118_MSN1266. 10 records from Plasm bearing foraminifera counts from multinet M31/2_MSN894. 341 records from Outer Hebrides Biological Recording Project - OHBRP Fungi, Lichens and Lower Plants Dataset - Outer Hebrides. 265 records from Geometry of coccolith Gephyrocapsa in sediment core K708-007. 1726 records from KTU Pinophyta. 3 records from Nannofossil abundance of Hole 22-212. 48 records from Census of calcareous nannofossil taxa expressed as percent of total number of individuals counted, ODP Site 114-703. 316 records from Planktic foraminifera counts of sediment core RC11-86. 110 records from BIRDRACE Angeliter Ornis. 239 records from Planktic foraminifera counts at CTD station M39/4_352CTD-11. 26 records from Plasm bearing foraminifera counts from M35/1_MSN1052. 160 records from Plasm bearing foraminifera counts from M35/1_MSN1068. 31 records from Total foraminifera counts of multinet M10/2_MSN322. 136 records from Total foraminifera counts of multinet PO247/2_MSN1380. 49 records from Microzooplankton (larger protists and small copepods) abundance measured on concentrated water bottle samples at station PS65/514-18. 22 records from Phytoplankton abundance measured in surface water during Charles Darwin cruise CD85. 322 records from Faunal assemblage of ODP Hole 101-633A (Table 2). 26 records from Coccolith counts of multinet M32/5_MSN988. 66 records from Nannofossil abundance of Hole 47-398D. 2 records from Nannofossil abundance of Hole 1-4. 21 records from Nannofossil abundance of Hole 18-173. 64 records from Range table from ostracoda in ODP Hole 151-910C. 5 records from Distribution of Quinqueloculina sp. in sediment core 13077-023. 1139 records from Shellfish (MNHM-MS). 29002 records from Computarización de la Colección Nacional de insectos Dr. Alfredo Barrera Marín del Museo de Historia Natural de la Ciudad de México. Coleóptera. 1 records from Miriapodi di alcune grotte della Campania. 819 records from CABI Bioscience Nematode Collection. 1 records from Occurrence of mammalia relicts at site Polch. 97419 records from CAS Ornithology (ORN). 137 records from Planktic foraminifera counts at CTD station PS55/019. 54 records from Pollen analysis and dinoflagellate cyst of sediment core IOW211660-6. 2 records from (Fig. 5) Pollen analysis of the Furo do Chato core. 168 records from Phytoplankton abundance during G. M. Dannevig cruise GMD90/18. 5 records from Tuttlinger Tag der Artenvielfalt. 177 records from BIRDRACE Die Kielbris. 92 records from Wiesen in der Grünen Mitte. 19 records from Nannofossil abundance of Hole 10-90. 3 records from Nannofossil abundance of Hole 2-9. 4 records from Nannofossil abundance of Hole 10-97. 39155 records from SBMNH Vertebrate Zoology. 13 records from Large protozoa abundance measured on concentrated water bottle samples at station PS58/061-3. 195 records from National Trust - Greater Horseshoe Bat records on National Trust properties in the South West. 6 records from Nano and microzooplankton abundance and biomass at station NBP96-04A-11-5. 4 records from Nano and microzooplankton abundance and biomass at station NBP97-01-23-2. 16 records from Phytoplankton abundance at station Sechin_2003-10-03_2, Casma, Peru. 22 records from Microzooplankton abundance measured on water bottle samples at station PS65/546-2. 15 records from (Table 2) Abundance of benthic foraminifers of sediment core PS2445-2. 521 records from Bayerische Donau - Leipheim. 216 records from Museu de Ciències Naturals de Barcelona: MCNB-ZG. 2 records from Nannofossil abundance of Hole 75-530A. 4 records from Bayerische Donau - Etterzhausen. 2777 records from Bryophyta Collection of Saitama Museum of Natural History. 2 records from Die Myriopodenfauna von Albanien und Jugoslavien. 235 records from Pseudoscorpions of Ireland. 18 records from Abundance, biovolume and biomass of heterotrophic dinoflagellates at station TT007_4-CTD45. 69 records from Microzooplankton abundance measured on water bottle samples at station PS58/049-3. 356 records from Biotope in Rheine - Aktion 350. 1 records from On the Chilopoda from Turkey. 315 records from Scleractinia specimens of Kuroshio Biological Research Foundation. 249 records from (Table 1) Relative abundance of selected benthic foraminifera in ODP Hole 104-644A. 204 records from Dinoflagellates and pollen of the Brito-Arctic Igneous Province flora, ODP Hole 104-642E. 56 records from Nemertini - SMF. 138 records from (Table 2a) Species composition of planktonic foraminiferas in bottom sediments from Core AK6-434-1. 1187 records from Florística y biogeografía de algunos bosques mesófilos de la Huasteca Hidalguense: Fase II (Tlahuelompa y Eloxochitlán). 15663 records from Leiner-Herbar Konstanz. 5 records from Nannofossil abundance of Hole 18-175. 2 records from Composition of the larger coarse silt fraction in surface sediments of the northwest African continental margin (Appendix Tab. 4). 394 records from Planktic foraminifera counts of sediment core V29-45. 503 records from Dinoflagellate cysts from sediment core PS2138-1. 8216 records from (Table 4) Distribution of benthic foraminifera in ODP Site 120-750. 1610 records from (Appendix A) Stratigraphic range and relative abundance of Paleogene planktonic foraminifera in ODP Hole 120-747A. 59 records from (Appendix 3) Stable oxygen isotope record of Globigerina bulloides and abundance of Neogloboquadrina pachyderma in sediment core MD99-2341. 1060 records from (Table 8) Distribution of planktonic foraminifers in ODP Hole 108-661A. 6 records from Molluscs in surface sediments off Sylt collected during Heincke cruise HE293. 145 records from Ostracoda abundance in DSDP Leg 87 holes. 679 records from (Appendix 1) DSDP Site 94-607 ostracode species census data. 6587 records from Ohio State University Tetrapod Division - Mammal Collection (OSUM). 137 records from Planktic foraminifera counts of sediment core V28-25. 10 records from Molluscs in surface sediments off Sylt collected during Heincke cruise HE241. 28 records from Heavy minerals of sediment core PS2719-1. 360 records from (Table 3d) Foraminiferal distribution chart of petroleum well Great-Eastern-1. 1381 records from Actualización de la base de datos de la colección mastozoológica de El Colegio de la Frontera Sur, San Cristóbal de las Casas. 56 records from Conocimiento de la macroflora marina de interés económico de las Costas de Yucatán. 104 records from Uso y monitoreo de los recursos naturales en el Corredor Biológico Mesoamericano (áreas focales Xpujil-Zoh Laguna y Carrillo Puerto) Murcielagos. 19 records from (Table 2) Range chart of calcareous nannofossils from Maud Rise sediment cores. 195 records from (Table 2) Abundance of planktonic foraminifera in ODP Hole 113-689B, small size fraction. 661 records from Ictiofauna de la Bahía de Banderas Nayarit, Jalisco y zonas adyacentes, México. 23836 records from Korea Bird Distribution Atlas Database. 73 records from Scottish Natural Heritage - Survey of slender naiad, Najas flexilis, in Loch of Butterstone and Loch of Craiglush. 34341 records from Historical hyperbenthos data (1987-2001) from the North Sea and some adjacent areas (EurOBIS). 54 records from Jeff Ogden Collection. 15879 records from Angiosperm specimens of Iwate Prefectural Museum. 1789 records from Relative abundance of planktic foraminifera in the 120 kyr time slice reconstruction of sediment core V22-174. 27 records from Microplankton abundance at Station MARCH-1998-GN36199804610MSB01 in the euphotic zone of the Aegean Sea in March 1998. Part 3 - coccolithophores and other groups. 1158 records from (Table 2) Absolute abundances of benthic foraminifera in ODP Site 120-748. 6704 records from Collection Crustacea - ZIM Hamburg. 5892 records from Inventario de los ropaloceros (Lepidoptera) de la Sierra Gorda, estado de Querétaro, México. 11027 records from Hymenopteran specimen database of Osaka Museum of Natural History. 1901 records from The University of Hong Kong Herbarium. 773 records from Neckartalsüdhang (Horb). 42 records from Schulgarten Paul-Schneider-Schule, Münster. 102 records from Planktic foraminifera abundance of Hole 67-498A. 19 records from Range table from planktonic foraminifers in ODP Hole 139-858C. 510 records from Range table from planktonic foraminifers in ODP Hole 146-888B. 268 records from Range table from benthic foraminifers in ODP Hole 159-959A. 612 records from (Tab. 8) Distribution of benthic foraminifera in Lower Cretaceous sediments of DSDP Hole 27-261, Argo Abyssal Plain, northwest of West Australia. 4051 records from Homoptera. 120 records from Phytoplankton abundance in surface water in July-August 1996, Callao, Peru. 6 records from Description of a new Episemion species (Cyprinodontiformes: Nothobranchiidae) from northern Gabon and southeastern Equatorial Guinea.. 163259 records from Herbario XAL del Instituto de Ecología, A.C., México (IE-XAL). 104 records from Antarctic Parborlasia corrugatus. 2392 records from (Table 3) Dinocyst ranges in ODP Hole 104-642D. 736 records from (Table 14) Distribution of planktonic foraminifers in ODP Hole 108-665A. 1152 records from (Table 1) Occurrence of Oligocene to Pleistocene benthic foraminifers in ODP Hole 121-754A. 320 records from Myxomycetes collection of the University of Eastern Finland. 16233 records from Crustacea specimens of Toyama Science Museum. 164 records from Abundance of dinoflagellates and ciliates at time series station Helgoland Roads, North Sea in 2008. 586 records from Inventario taxonómico de los hongos conidales saprobios del parque Yumka' en Villahermosa, Tabasco. 5125 records from Respaldo de las colecciones de tejidos del Museo de Zoología, Departamento de Biología Evolutiva, Facultad de Ciencias, UNAM (Aves). 1 records from Akita Prefectural Museum＋Bryozoans Specimens of Akita Prefectural Museum. 15 records from Averages and ranges of paleoenvironmental proxy records of ODP Hole 108-658C (Table 1). 87 records from (Table 5) Stratigraphic distribution of calcareous nannofossil taxa in ODP Hole 149-898A. 14830 records from Parasitic Platyhelminthes Collections. 3210 records from HerbarioHerrerense. 539 records from Bay of Puck dataset (EurOBIS). 44501 records from Canadian National Collection (CNC) of Insects, Arachnids and Nematodes. 7 records from (Table 4) Concentrations of PCBs and MeSO2-PCBs in adipose tissue of polar bears (Ursus maritimus) between 1991-2007. 81037 records from Museum of Zoology, University of Navarra. 4312 records from Distribution of ostracoda in the lower Cretaceous succession of ODP Hole 80-549 (Figure 3). 2940 records from RSPB - Cirl bunting national surveys in the UK (SCARABBS). 1374 records from (Table 11) Ranges of benthic foraminifers through the Oligocene in ODP Hole 115-709C. 14842 records from Real Jardin Botanico, Madrid: MA-Lichen. 1 records from Hypogeoppia dungeri, a new species of the Oppiellinae (Acari, Oribatida, Oppiidae). 6629 records from Benthic biodiversity along the central coast in the Brazilian EEZ (OBIS South America, BRAZIL) (OBIS South America, BRAZIL). 29500 records from Fish Collection of Kanagawa Prefectural Museum of Natural History. 2320 records from Planktic foraminifera assemblage of sediment core ELT49.018-PC. 8523 records from Distribution of planktic foraminifers of core RC24-16. 12113 records from Distribution of planktic foraminifers and SST of sediment core GIK15637-1. 1530 records from Distribution of planktic foraminifera of sediment core M33/1_SL_EAST. 23 records from Microplankton abundance in the euphotic zone of the Aegean Sea in September 1998. 5276 records from Biodiversidad de la Sierra Tarahumara. Lepidoptera: Mimallonoidea, Lasiocampoidea, Bombycoidea y Pyraloidea. 47 records from Distribution of calcareous nannofossils in the lower sequence of the CIROS-1 sediment core (Table 2). 15709 records from Museo Nacional de Ciencias Naturales, Colección de Malacología. 101 records from CNAN/Escorpiones Estado de Mexico. 1698 records from Distribution of planktic foraminifers of core RC10-62. 10 records from (Table A) Abundance of species detected in mussel beds within hydrothermal fields on the Mid-Atlantic Ridge. 1678 records from (Table 3) Ranges of benthic foraminifers from the late Eocene through the Oligocene in ODP Hole 115-707A. 4071 records from Real Jardin Botanico, Madrid: MA-Hepat. 261 records from Planktic foraminifera distribution of sediment core TRI171-24. 305 records from (Table IIIb) Planktic foraminifera abundances in the earliest Paleocene sample interval of DSDP Hole 86-577 from the Shatsky Rise, western Pacific Ocean. 150 records from UC Davis Department of Anthropology Museum. 4 records from Oribatids from Switzerland IX (Acari: Oribatidae, Mycobatidae 2) (Acarologica Genavensia CI). 2475 records from Artenvielfalt auf der Weide - GEO-Hauptveranstaltung in Crawinkel. 26 records from Microplankton abundance at Station MARCH-1997-GN36199704603MNB04 in the euphotic zone of the Aegean Sea in spring 1997. Part 3 - coccolithophores and other groups. 57 records from Occurrence of mammalia relicts at site Tornewton Cave. 138 records from Planktic foraminifera abundance of Hole 26-250A. 5 records from Planktic foraminifera abundance of Hole 19-184B. 166 records from Planktic foraminifera abundance of Hole 9-82A. 87929 records from Herbario de la Universidad de Sevilla, SEV. 53 records from Planktic foraminifera assemblage in sediment core GIK23041-1. 307 records from NABU Naturschutzhof Netttetal (Sassenfeld) e.V.. 122 records from Microplankton abundance at Station SEPT-1997-GN36199704605MSB07 in the euphotic zone of the Aegean Sea in September 1997. Part 2 - dinoflagellates. 151 records from Occurrence of mammalia relicts at site Stadel im Hohlenstein. 14 records from Benthic foraminifera abundance of Hole 42-378. 14 records from Range table from benthic foraminifers in ODP Hole 178-1101A. 22 records from Dinoflagellate abundance of Hole 14-144. 14763 records from Herp Collection. 8980 records from MEXU/Tipos de plantas vasculares. 906 records from Percentages of planktonic foraminifera species in sediment core V15-168. 187 records from (Table Ib) Planktic foraminifera abundances in the earliest Paleocene sample interval of DSDP Hole 74-528 on the Walvish Ridge, South Atlantic. 88 records from (Appendix A2) Cenomanian benthic foraminifera of ODP Site 207-1260. 336 records from Foraminifera abundance of Hole 24-237. 420 records from (Table 4) Relative abundances of planktonic foraminifera in Pliocene sediments of ODP Site 161-975 in the Mediterranean Sea. 302015 records from University of Alberta Entomology Collection (UASM). 7 records from Grundwasserlebensraum im Englischen Garten (München). 544 records from (Table AT6) Planktonic foraminiferal stratigraphy of ODP Hole 182-1130B. 1262 records from Isle of Wight Local Records Centre - IOW Natural History & Archaeological Society Marine Invertebrate Records 1853- 2011. 12 records from Microplankton abundance at bottle station SEPT-1999-K2. 58 records from Occurrence of mammalia relicts at site Sandalja II. 8 records from Occurrence of mammalia relicts at site Sernesul Rece Cave. 109 records from Occurrence of mammalia relicts at site Pestera Hotilor. 48 records from Planktic foraminifera abundance of Hole 47-397. 94 records from Planktic foraminifera abundance of Hole 63-468A. 525 records from Benthic foraminifera abundance of Hole 40-360. 37 records from Range table from benthic foraminifers in ODP Hole 182-1128D. 34 records from Occurrence of mammalia relicts at site Felsdach Inzighofen. 1 records from Myriopoden von Kreta, nebst Bitraegen zur allgemeinen Kenntnis einger Gattungen. 73 records from (Table 17) Calcareous nannofossil occurrences in ODP Hole 130-804C. 4 records from Results of diatom analysis of Hole 302-M0004A. 146382 records from Swedish Board of Fisheries (Fiskeriverket) - Institute of Coastal Research. 1 records from Revision der Ceratozetidae, 5. Ceratozetes thienemanni WILLMANN (Arach., Acari, Oribatei). 10 records from Distribution and habitat of the Laotian Rock Rat Laonastes aenigmamus Jenkins, Kilpatrick, Robinson & Timmins, 2005 (Rodentia: Diatomyidae) in Vietnam. 600 records from Range table from planktonic foraminifers in ODP Hole 155-930B. 150 records from Phytoplankton abundance in surface water in October 1996, Pisco, Peru. 631 records from Distribution of benthic foraminifera on sediment core sediment core PS2458-4. 13628 records from ABBBS Bird Banding records from the Australian Antarctic Territory and Heard Island.. 1268 records from Makira. 119 records from Cambridgeshire & Peterborough Environmental Records Centre - CPERC Black Poplar survey. 1 records from Beitrage zur Kenntniss paläarctischer Myriopoden. XV. Aufsatz: Lithobiiden aus Bosnien, Herzogovina und Dalmatien. 280 records from (Figure 1d) Distribution of planktonic foraminifera in bottom sediments of Core Vy20-3202. 7 records from On the centipedes (Chilopoda) of the Republic of Macedonia. 9 records from Diaphoromyrma, a new myrmicine ant genus (Hymenoptera: Formicidae) from North Eastern Brazil. 16 records from Occurrence of mammalia relicts at site Crayford. 114 records from Planktic foraminifera abundance of Hole 18-179. 182 records from Planktic foraminifera abundance of Hole 28-264A. 404 records from Planktic foraminifera abundance of Hole 94-609B. 836 records from Distribution of Upper Cretaceous deep water agglutinated foraminifera in sediments of the North Atlantic and its marginal seas (Tab. 1). 10 records from Dinoflagellate abundance of Hole 81-552. 42 records from Benthic macrofauna abundance in surface sediments of the east Greenland continental slope (79° N section). 1497 records from Foraminifera abundance of Hole 57-438A. 1607 records from Range table from benthic foraminifers in ODP Hole 162-986D. 60 records from (Tab. 5) Distribution of benthic foraminifera in Lower Cretaceous sediments of DSDP Hole 13-120, Gorringe Bank southwest of Spain. 25 records from (Fig. 9B) Compiled data of profile Pré-Guittard, SE France. 1031 records from (Table 4) Carbon flux, paleoproductivity, relative abundance of foraminifera on sediment core PS2837-5. 31 records from (Table 3) Oxygen and carbon isotope ratios of Globigerinoides sacculifer of ODP Hole 134-828A. 540 records from (Appendix 3) Abundances of benthic forminifera in DSDP Hole 74-525A. 26 records from Akysis pulvinatus, a new species of catfish (Siluriformes: Akysidae) from southern Thailand.. 67 records from (Table 2) Constituents of the sand-size fraction of ODP Site 139-857. 1 records from Deux especes nouvelles pour la science du genre Eupolybothrus Verhoeff (Lithobiomorpha: Ethopolinae). - Two new species for the science in the genus Eupolybothrus Verhoeff (Lithobiomorpha: Ethopolinae). 3719 records from (Figure 4) Stratigraphic distribution of planktonic foraminifera in DSDP Hole 93-604. 59 records from Range table from planktonic foraminifers in ODP Hole 177-1089D. 4 records from Range table from benthic foraminifers in ODP Hole 194-1193A. 42 records from (Tab. 10) Distribution of benthic foraminifera in Lower Cretaceous sediments of DSDP Hole 32-303A, Japanese Magnetic Lineations east of Japan. 71 records from Range table from silicoflagellates, ebridians and actiniscidians in ODP Hole 151-908A. 4579 records from Estacion Biologica Donana - CSIC, Anfibios (EBD_HERP). 745 records from Gunma Museum of Natural History, Mammal Specimen. 42455 records from Collection Aves (bird skins) SMF. 13 records from Collection Reptilia fossil SMF. 1740 records from Monitoring data from the federal state Berlin (Germany). 6668 records from Algae (NSMK-AG). 15768 records from SARCA. 5 records from Chenopodium vulvaria. 528 records from (Table 3) Relative abundances of benthic foraminifera in ODP Hole 128-799A. 27988 records from Argyll Bird Club - Bird records for Argyll for the years 2002 and 2003. 18 records from Fossil occurrence from planktonic foraminiferas from IODP Hole 315-C0001I. 150 records from Redescription and generic placement of the spider Cryptachaea gigantipes (Keyserling, 1890) (Araneae: Theridiidae) and notes on related synanthropic species in Australasia. 178 records from RSPB - Corn bunting surveys on the Western Isles. 301 records from Gyeryonsan Natural History Museum Bird . 26 records from Akysis longifilis, a new species of catfish (Teleostei: Akysidae) from Myanmar.. 124 records from (Table S1) Distribution of Florisphaera profunda in surface sediment samples. 1 records from Arthropoden aus südostalpinen Höhlen.. 33 records from Waldstück am Schullandheim Bad Bederkesa. 24 records from Biopearl expedition: SeaStars (Echinodermata, Asteroidea). 49 records from Museu Paraense Emilio Goeldi - Uropygi Collection. 54373 records from Inventaire National du Patrimoine Naturel : Atlas des poissons d'eau douce de France métropolitaine (2011). 2730 records from (Table AT5) Planktonic foraminiferal stratigraphy of ODP Hole 182-1130A. 58327 records from Inventaire National du Patrimoine Naturel : Fichier communal des ongulés. 1 records from Die Gattung Carabodes C. L. Koch 1836 in der schwedischen Bodenfauna (Acar. Oribat.). 1034 records from (Table 3) Distribution of Campanian-Maestrichtian calcareous foraminifers in DSDP Hole 78-543A. 31251 records from International Fossil Shell Museum (NL) - Mollusca Collection. 39 records from Bonner Schülerinnen am Rodder Maar. 22 records from A new species of snapper (Perciformes: Lutjanidae) from Brazil, with comments on the distribution of Lutjanus griseus and L. apodus.. 707 records from Merseyside BioBank - Merseyside BioBank Active Naturalists (verified). 1 records from Nothrus farinosus. 72636 records from Insect Collection of Taiwan Forestry Research Institute. 9 records from Rivulus uakti sp. n. and R. amanapira sp. n. (Teleostei: Cyprinodontiformes: Rivulidae): two new species from the upper Rio Negro, Brazilian Amazon.. 6314 records from UWYMV Mammal Collection (Arctos). 38841 records from Herbier de Strasbourg. 45 records from Flusswerder in der Weser (Hameln). 133 records from Wulfsmuehle/Pinnau. 83 records from Birdrace-Die_Vogelscheuchen-Herford. 3 records from Nannofossil abundance of Hole 3-17. 8 records from Cirrhigaleus australis n. sp., a new Mandarin dogfish (Squaliformes: Squalidae) from the south-west Pacific.. 38 records from Phytoplankton abundance and species composition in the Gulf of Naples in June 1999 at station MCSSII-phyto75-83. 2 records from Two new species of Baeus (Hymenoptera: Scelionidae) from southeastern Brazil parasitoids of Anelosimus (Araneae: Theridiidae).. 5 records from (Table 2) Abundance, preservation, and distribution of calcareous nannofossils in ODP Hole 135-840A. 108342 records from Ornithology Collection Passeriformes - Royal Ontario Museum. 28 records from Two new species of Pamphobeteus Pocock 1901 (Araneae: Mygalomorphae: Theraphosidae) from Brazil, with a new type of stridulatory organ. 204 records from (Table 8) Sample mass, sand fraction and relative abundances of planktonic foraminifera in ODP Holes 127-794A and 127-197B. 259 records from (Table 2) Abundances of planktonic and benthic foraminifera in ODP Hole 130-807A. 19309 records from Mammal collection, Natural History Museum, University of Oslo. 143 records from BIRDRACE Die Laufenten. 448 records from Benthic foraminifera counts of sediment core GIK23359-2. 40 records from Nannofossil abundance of Hole 21-205. 75 records from (Table S1c) Measured tomographic parameters for Nuttallides truempyi during the PETM for ODP Site 208-1263. 23300 records from Central African Plants. 248 records from (Table 3) Distribution of Cretaceous nannofossils at DSDP Hole 79-547A. 3 records from New synonym of Tipula (Vestiplex) wahlgrenana Alexander, 1968 (Diptera: Tipulidae). 227 records from Colección de Salamandras Museo de La Salle Bogotá (MLS). 356 records from Morphologische Daten von Puffinus creatopus. 1 records from Nothrus segnis. 13909 records from Albany Museum. 27639 records from Cicadelidos (Hemiptera: Cicadellidae) de Colección Entomológica del Instituto Alexander von Humboldt. 601 records from Dinoflagellate cyst species of sediment core GeoB10732-3. 70738 records from University of Alberta Vascular Plant Herbarium (ALTA). 5 records from Specimen records associated with "A troglomorphic spider from Java (Araneae, Ctenidae, Amauropelma). 1385 records from Countryside Council for Wales - Amphibian & Reptile Licence Return Data . 38 records from Fourteen new species of Pseudisobrachium (Hymenoptera, Bethylidae) from Atlantic rain forest of Espírito Santo, Brazil.. 3359932 records from Dutch Foundation for Applied Water Research (STOWA) - Limnodata Neerlandica. 1698 records from RSPB - Red-throated diver national surveys in Scotland - raw data (SCARABBS). 3268 records from (Table 1) Distribution of early Eocene to early middle Eocene benthic foraminifera in DSDP Hole 93-605. 31 records from Regenwasserabfangbecken. 13 records from Eintauchen in die Natur /Harraser Weg (AWO - Kita Oberheldrungen). 17 records from Bachrenaturierung Littfe. 54 records from Living benthic foraminifera at station M33/1_MC-25 (EAST), size fraction >125 µm. 53 records from Living benthic foraminifera at station M33/1_MC-13 (WAST-T), size fraction 63-125 µm. 149 records from Plasm bearing foraminifera counts from M35/1_MSN1046. 132 records from Plasm bearing foraminifera counts of multinet M21/1_MSN613. 115 records from Total foraminifera counts of multinet PO247/2_MSN1382. 49 records from Distribution of planktic foraminifera (250-500 µm) of box sediment core PS1246-2. 238 records from Revision der europäischen Gattungen und Arten der Familie Brachychthoniidae (Acari, Oribatei) Teil 1. Allgemeiner Teil: Brachychthoniidae Thor, 1934. Spezieller Teil: Liochthonius v. d. Hammen, 1959, Verachthonius nov. gen. und Paraliochthonius nov. gen.. 11371 records from Herbario Museo de La Salle Bogotá (MLS). 882456 records from South Australia Fauna Observations. 1 records from Haslauer Moor. 68 records from Abundance of dead benthic foraminifera in sediment core CD86_01_BC1. 62 records from Total foraminifera counts of multinet M21/4_MSN705. 73 records from Plasm bearing foraminifera counts of multinet PO247/2_MSN1376. 26 records from Meiofauna abundances at the Arctic Håkon Mosby Mud Volcano (HMMV) of sediment core PS64/367-1. 31 records from Nannofossil abundance of Hole 4-23. 10 records from Nannofossil abundance of Hole 38-338. 8906 records from Hymenoptera de la Colección Entomológica del Instituto Alexander von Humboldt. 4 records from A new carpenter ant, Camponotus parabarbatus (Hymenoptera: Formicidae) from India. 9 records from (Appendix B) Relative abundance of benthic foraminifera morphotypes in ODP Hole 138-844C. 36974 records from Environment Agency - Environment Agency Rare and Protected Species records v1. 360 records from (Figure 1g) Distribution of planktonic foraminifera in bottom sediments of Core Vy20-3174. 34502 records from Merseyside BioBank - North Merseyside Birds (verified). 151 records from Molluscan fauna of Gueishan Island of Taiwan. 464 records from Lepidoptera collection, NTNU, Trondheim. 453 records from Colección de Fauna Marina del Centro Oceanográfico de Málaga (I.E.O.): CFM_IEOMA. 99 records from BIRDRACE TEAM BO-BACHTER. 66 records from Von der Nutzung zur Natur. 31 records from Benthic foraminiferal assemblage (Rose Bengal stained) in MUC OB10-K, size fraction >150 µm. 5 records from Nannofossil abundance of Hole 77-536. 1933 records from Gloucestershire Environmental Data Unit - Gloucestershire BAP Priority Species - Dormouse. 94 records from Birdrace-Resopal_Altkreis_Dieburg-Team-Darmstadt/Dieburg. 5 records from Feuchtwiese. 7 records from Planktic foraminifera counts of multinet M21/5_MSN732. 93 records from Distribution of planktic foraminifera (125-250 µm) of box sediment core PS1243-2. 4 records from Sarcodine counts and carbon biomass at station TT012_4-CTD6. 68 records from (Table 3) Macro- and meiofaunal species abundance in box core samples from the North Pacific Ocean. 95 records from Nannofossil abundance of Hole 15-149. 3 records from Nannofossil abundance of Hole 37-333A. 4 records from (Figure 10) Relative abundance of nannoliths at DSDP Hole 62-466. 1 records from Identification of the species of Gnamptogenys Roger in the Americas.. 274 records from Bernhardsthal. 179 records from Total foraminifera counts from multinet M31/3_MSN906. 66 records from Total foraminifera counts from M35/1_MSN1064. 68 records from Microzooplankton (larger protists and small copepods) abundance measured on concentrated water bottle samples at station PS65/593-9. 7 records from Size fractioned abundances and carbon biomasses of heterotrophic protists at station NIOP-B1_230-9. 11 records from Microzooplankton abundance and biomass at station TT045_2-1. 20 records from (Table T2) Dinoflagellate cyst occurrence in neogene sediments of ODP Hole 178-1096C. 1038 records from (Appendix 2-4) Distribution of planktonic foraminifera in late Neogene sediments of DSDP Site 31-292 in the western Pacific Ocean. 2905 records from (Table A.01) Planktic foraminiferal census data of sediment core GIK23414-9. 5265 records from Lower Albian, Niveau Paquier range chart of nannofossils in SE France. 12 records from Ostracoda abundance of Hole 32-306. 405 records from (Table 5) Range chart of benthic and planktonic foraminifera of ODP Site 127-797. 442 records from Inventaire National du Patrimoine Naturel : CBN Brest. 233 records from Total foraminifera counts from M35/1_MSN1044. 46 records from Plasm bearing foraminifera counts of multinet M27/2_MSN884. 47 records from Foraminifera species abundances from tow TT007_3-MOC6. 140 records from Distribution of planktonic foraminifera of sediment core SH1972_17. 18 records from Abundance of radiolaria at station LV28-43-2. 126 records from Benthic foraminiferal number, diversity, and species abundance of size fraction 63-125µm across sapropel S6 in core M40/4_KL51 from the lower bathyal of the western Levantine Basin. 148 records from Total foraminifera counts of multinet M21/6_MSN767. 64 records from Plasm bearing foraminifera counts of multinet PO247/2_MSN1391. 24 records from Abundance and carbon biomass of phytoplankton at station TT007_10-CTD130. 2 records from Nano and microzooplankton abundance and biomass at station NBP97-01-13-5. 15 records from (Table 2) Abundance of benthic foraminifers of sediment core PS2177-3. 76 records from Coccoliths in sediment core PS1533-3. 46 records from Phytoplankton abundance measured on water bottle samples during Jan Mayen cruise JM3. 30 records from Assemblage of living benthic foraminifera in sediment core CD145_55830#3, 63-150 µm. 201 records from Assemblage of living benthic foraminifera in sediment core GeoB4912-4. 126 records from Total foraminifera counts from M35/1_MSN1050. 66 records from Total foraminifera counts from M35/1_MSN1059. 121 records from Total foraminifera counts of multinet M21/2_MSN647. 61 records from Microzooplankton (larger protists and small copepods) abundance measured on concentrated water bottle samples at station PS65/546-19. 3 records from Sarcodine counts and carbon biomass at station TT011_5-CTD64. 118 records from Phytoplankton abundance at Station Sechin_EP2 in 2002, Casma, Peru. 13 records from Phytoplankton abundance at station Sechin_2003-08-27_1, Casma, Peru. 16 records from Distribution of meiobenthos in sediment core M19_246-2 of the northeastern Atlantic (Table 1). 14 records from (Table 2) Abundance of benthic foraminifers of sediment core PS2187-5. 69 records from Naturpark Kottenforst-Ville 18.6.09. 19 records from Smear slide analysis on sediment core GeoB4214-1. 6494 records from Open Mosaic Habitat Survey Group - Invertebrates recorded during Open Mosaic Habitat survey in England and Wales (2012). 11 records from Diatom abundance measured on water bottle samples at station PS58/092-3. 85 records from Distribution of planktic foraminifera (125-250 µm) of box sediment core GIK23059-2. 36 records from A revision of the genus Medmassa Simon, 1887 (Araneae: Corinnidae) in the Afrotropical Region. 121 records from (Table 2, 3) Macro- and meiofaunal specimens abundance, organic carbon content and analysis of coarse clasts of box core samples from the North Pacific Ocean. 1658 records from Relative abundances of twenty-eight dominant benthic foraminifera species of DSDP Hole 23-219 (Table 1s). 31967 records from MfN - Fossil invertebrates Ia. 7 records from Nannofossil abundance of Hole 49-409. 16604 records from Iberian Odonata distribution: data of the BOS Arthropod Collection (Univ. Oviedo, Spain). 21158 records from Birds Specimens. 48394 records from Bird specimens. 30 records from Visual Plants (144.41.33.158) - Private collection of Manfred Kueppers. 441 records from Planktic foraminifera distribution of sediment core 75KS76. 6216 records from Distribution of diatoms and ostracods in sediment samples collected between 1995 and 2010 in the San Francisco Bay coastal system. 10 records from Abundance of empty diatom frustules measured on water bottle samples at station PS58/108-1. 51 records from Nannofossil abundance in sediment core PS1293-4. 45 records from Abundance of three benthic foraminifera species in surface sediments of a North-eastern Atlantic Abyssal Locality. 5 records from Distribution of Quinqueloculina sp. in sediment core 13077-070. 15494 records from (Table 6) Stratigraphic ranges and relative abundances of Paleogene planktonic foraminifers and other selected organisms in ODP Hole 114-703A. 1215 records from Computarización de la xiloteca Dr. Faustino Miranda del Instituto de Ecología, AC. 2088 records from Benthic foraminifera of sediment core MD99-2286. 21 records from Nannofossil abundance of Hole 24-232A. 75 records from Range table from ostracoda in ODP Hole 159-960C. 20 records from Meiofauna abundance in sediment core 13077-058. 45896 records from Angiospermatatophytina Collection of Saitama Museum of Natural History. 91 records from Admiralty Bay Benthos Diversity Data Base (ABBED). Tanaidacea.. 197 records from (Table 7) Relative abundance of benthic foraminifera in ODP Hole 112-683A. 9 records from Diatom abundance measured on water bottle samples at station PS58/045-2. 51 records from Nannofossil abundance in sediment core PS1291-4. 14108 records from Rådgivende Biologer. 630 records from (Figure 3) Distribution chart of benthic foraminifers in ODP Site 126-790. 2245 records from (Fig. 3a-e) Distribution of planktonic foraminifera in surface sediments. 7245 records from (Figure 5) Stratigraphic ranges of selected planktonic foraminifers at ODP Hole 101-627B. 10570 records from Bumblebees, cuckoobees and butterflies in southern Poland. 5 records from (Table 2) Biomass of cysts and active infusoria in waters of the Peru coast area. 38838 records from Collection Malakologie - SNSD. 1046 records from NBM Insects. 6723 records from NOAA HML Tidal Creek Database. 3139 records from Foraminifera and stable isotopes of sediment core PS2076-3. 2 records from Microplankton abundance at Station MARCH-1998-GN36199804611MNB03 in the euphotic zone of the Aegean Sea in March 1998. Part 1 - diatoms. 39 records from Megafauna abundance and biomass from trawl samples obtained during cruise DI231. 741 records from Biogeographic distribution of Antarctic and sub-Antarctic Mysida. 33 records from (Table 3) Sr-Nd-Pb isotope ratios of selected Cocos Plate samples. 1824 records from (Table 6) Distribution of live benthic foraminifera in deep-sea surface sediments of the Scotia Sea, part 2. 8525 records from Literary descriptions of Iranian lizards. 2000 records from Biodiversidad de los crustáceos dulceacuícolas del centro de Nuevo León y noroeste de Tamaulipas. 84270 records from Actualización y enriquecimiento de las bases de datos del proyecto de evaluación y análisis geográfico de la diversidad faunística de Chiapas. 10567 records from University of Alberta Museums, Ichthyology Collection. 3 records from Diatom abundance of Hole 60-453. 15 records from Meiofauna abundance in sediment core 54301-016. 6909 records from Herbario del Departamento de Biología Vegetal (Botánica) de la Universidad de La Laguna, Tenerife (TFC). 67384 records from University of Alberta Museums, Vascular Plant Herbarium. 6680 records from SOMBASE PYCNOGONIDS. 241 records from (Table 2) Distribution of late Miocene to Pleistocene calcareous nannofossils in ODP Hole 105-646B. 1188 records from (Table 15) Distribution of planktonic foraminifers in ODP Hole 108-666A. 248496 records from RSPB - Bird Conservation Targeting Project (BCTP) in the UK, archived data (2001-2008) . 1675 records from (Table 7) Distribution of dead benthic foraminifera in deep-sea surface sediments of the Scotia Sea, part 1. 56 records from Distribution of species of planktic foraminifera in bottom sediments from Core AK32-3333. 6554 records from Mammalia fossil Kleinsäuger - SMF. 39 records from (Table 1) Distribution of foraminiferal tests in recent sediments of interior seas of Malay Archipelago. 3512 records from (Table 3) Plio-Pleistocene benthic foraminifera of ODP Hole 107-653A. 2255 records from Evaluación de la ictiofauna en las áreas focales del corredor biológico costero-Yucatán. 216 records from Echinoderms in surface sediments off Sylt collected during Heincke cruise HE236. 13 records from (Table 4a) Abundances of Globorotalia menardii in sediment core INMD-104BX. 38 records from (Table 3) Cretacoeus calcareous nannofossils from ODP Hole 123-766A. 19 records from Pollen profile from Achenhang. 2304 records from Historia natural del parque ecológico estatal de Omiltemi, Chilpancingo, Guerrero, México. 52 records from (Table 3) Stratigraphic distribution of calcareous nannofossils from ODP Hole 123-765C. 414 records from Naturschutzstation Schmidsfelden. 546 records from 20 Jahre Naturschutzgebiet Dreienberg. 2 records from Die Myriopodenfauna von Albanien und Jugoslavien. 1351 records from Pteridoflora de Morelos. 38100 records from Natural Geography In Shore Areas (NaGISA) Dataset. 1403 records from Relative abundance of planktic foraminifera in the 120 kyr time slice reconstruction of sediment core RC13-205. 497 records from Relative abundance of Quaternary foraminifera of sediment core CRP-1 (App. 1). 10 records from Microplankton abundance in the euphotic zone of the Cretan Sea at Station NOVEMBER-1994-D4. 1441 records from (Table 1) Count data of organic-walled dinoflagellate cysts in surface sediment samples from the Benguela System. 65 records from Occurrence of mammalia relicts at site Vogelherd/Lonetal. 23 records from Occurrence of mammalia relicts at site Ochoz Cave. 329 records from Planktic foraminifera abundance of Hole 60-458. 88 records from Range table from planktonic foraminifers in ODP Hole 167-1021B. 666 records from Range table from planktonic foraminifers in ODP Hole 171-1051A. 11340 records from (Table 3) Stratigraphic ranges and relative abundances of Paleogene planktonic foraminifers and other selected organisms in ODP Hole 114-699A. 251 records from Evaluación del estatus de los géneros Pereskiopsis y Pereskia (Cactaceae) en los Apéndices de la CITES. 10 records from (Table 1) Position of the upper and lower boundaries of the seasonal thermocline, depths of the main maxima and values of biomass and abundance of Rhizosolenia calcar-avis and Pronoctiluca pelagica at these depths, Black Sea, October 1992. 18 records from (Table 3) Distribution of middle Eocene calcareous nannofossils in ODP Hole 149-897C. 28 records from (Table 1) Mineralogy and abundance of Truncorotalia tosaensis in ODP Hole 194-1195A. 6383 records from RSPB - RSPB Reserves breeding bird surveys. 106 records from Visual Plants (144.41.33.158) - Plants from the Kakamega Forest, Kenya; Dana Uster. 836 records from Visual Plants (144.41.33.158) - Botanical garden, University of Hohenheim, Germany. 18656 records from Coleção Entomológica Moure e Costa. 1535 records from Mushroom Collection in BCRC. 6854 records from Lepidópteros Bombicoides de México (Lepidoptera: Bombycoidea: Saturniidae, Sphingidae) (UCOL). 2087 records from GEO-Hauptveranstaltung (NLP Harz / Hochharz). 1291 records from Sudeniederung (Amt Neuhaus), Landkreis Lüneburg. 25 records from Range table from planktonic foraminifers in ODP Hole 171-1052D. 257 records from RSPB - Common scoter national breeding surveys in Britain (SCARABBS). 3724 records from Ibaraki Nature Museum, Bryophyta collection. 3 records from Meiofaunal abundance, biomass, taxon richness and indices of nematode diversity of samples from the Santa Maria di Leuca Bank (southern Adriatic margin). 170 records from (Fig. 3) Relative abundance of Emiliania huxleyi in sediment core MD99-2343. 14885 records from Ontario Breeding Bird Atlas 1981-1985. 72615 records from Marine and Coastal Management - Demersal Surveys (years 1991-1995) (AfrOBIS). 591 records from Alan Wormington Collection. 21333 records from Coleccion de Herpetologia, MZFC-UNAM. 40 records from Animal observations. 27 records from Microplankton abundance at Station MARCH-1997-GN36199704601MSB02 in the euphotic zone of the Aegean Sea in spring 1997. Part 2 - dinoflagellates. 68 records from Planktic foraminifera abundance of Hole 4-29B. 180 records from Foraminifera abundance of Hole 58-442A. 186 records from (3) Sea Surface Temperature (SST) reconstructed from the percentage of Neogloboquadrina pachyderma sinistral in sediment core MD02-2488 during the period 50-140 ka. 10741 records from Japan Collection of Microorganisms, RIKEN BioResource Center. 683018 records from The System-wide Information Network for Genetic Resources (SINGER). 92 records from Zwei Flüsse - eine Stadt (Villingen-Schwenningen). 19 records from Microplankton abundance at Station MARCH-1997-GN36199704603MNB03 in the euphotic zone of the Aegean Sea in spring 1997. Part 2 - dinoflagellates. 18918 records from (Table 1) Distribution of benthic and planktonic foraminifers at DSDP Hole 28-270. 18 records from Range table from planktonic foraminifers in ODP Hole 182-1128A. 17 records from Range table from benthic foraminifers in ODP Hole 159-962B. 38 records from Dinoflagellate abundance of Hole 71-512. 3096 records from Biological Records Centre - Mosquito Recording Scheme . 31 records from Description of a new species of Acestridium (Siluriformes: Loricariidae) from Colombia.. 593 records from Mamíferos voladores laguna El Tinije. 29367 records from Geographic distribution of dinoflagellate cysts in surface sediments. 362174 records from The Flora of County Wexford. 16007 records from NCOS1959_Mollusca (OBIS China). 11941 records from Universitat de València, Colecciones de Criptógamas: VAL_Lich. 234 records from Werremündung im Schwarzatal. 328 records from Range table from planktonic foraminifers in ODP Hole 170-1040C. 2 records from Range table from planktonic foraminifers in ODP Hole 178-1095A. 1 records from Range table from planktonic foraminifers in ODP Hole 178-1095D. 910 records from (Table 2) Distribution of benthic foraminifera on sediment core PS2138-1. 760 records from Relative abundance of dead benthic foraminifera of sediment core M5/2_88MC. 405 records from Freiburger Netzwerk Artenvielfalt. 32916 records from Insect specimen database of Atugi City Museum. 2 records from Eine neue Art der Gattung Suctobelba Paoli (Suctobelba vera n. sp.) aus Deutschland (Acarina: Oribatei). 926 records from John Muir Trust - Knoydart Bryophytes, 1990. 1 records from Oribates coracinus. 151334 records from Gothenburg Herbarium - General (GBIF:IH:GB:Herbarium). 251 records from Foraminifera abundance of sediment core IN68-28. 127 records from Industriegebiet (Kempen). 43 records from Vogelstimmenführung durch den Tiergarten. 202 records from Tiergarten Straubing. 672 records from Range table from planktonic foraminifers in ODP Hole 155-938A. 960 records from (Table 11) Benthic foraminifera in Pliocene sediments of DSDP Hole 90-591. 12 records from Range table from planktonic foraminifers in ODP Hole 169-1038F. 30 records from Range table from planktonic foraminifers in ODP Hole 170-1042B. 152 records from Range table from planktonic foraminifers in ODP Hole 177-1088B. 4 records from Range table from planktonic foraminifers in ODP Hole 183-1137A. 8 records from Benthic foraminifera abundance of Hole 96-622. 91 records from Range table from benthic foraminifers in ODP Hole 188-1165B. 1794 records from Herbarium BSG Lichenes. 10395 records from Type herbarium, Göttingen (GOET). 152 records from Investigación y manejo para la conservación de tortugas amenazadas de los humedales llaneros. 10 records from Microplankton abundance in the euphotic zone of the Aegean Sea at Station SEPT-1998-MNB6. 68 records from Occurrence of mammalia relicts at site l´Abri du Morin. 82 records from Planktic foraminifera abundance of Hole 14-144A. 107 records from Planktic foraminifera abundance of Hole 1-2. 47 records from Planktic foraminifera abundance of Hole 15-150. 53 records from Planktic foraminifera abundance of Hole 29-281A. 22 records from Planktic foraminifera abundance of Hole 27-259. 15 records from Range table from benthic foraminifers in ODP Hole 189-1172D. 156948 records from NBI. 63 records from Occurrence of mammalia relicts at site Smolucka Pecina. 58 records from Range table from planktonic foraminifers in ODP Hole 141-861A. 24 records from Range table from planktonic foraminifers in ODP Hole 146-889B. 91 records from Benthic foraminifera abundance of Hole 84-569A. 102 records from Range table from benthic foraminifers in ODP Hole 146-888A. 468 records from Phytoplankton abundance in surface water in February 1998, Chimbote, Peru. 54 records from Outer Hebrides Biological Recording Project - OHBRP Vertebrates (except birds and restricted records) Dataset - Outer Hebrides. 6 records from (Table 1) Nesting characteristics of greater snow geese (Chen caerulescens atlanticus) on Bylot Island between 1995-2005. 11 records from Etmopterus burgessi sp. nov., a new species of lanternshark (Squaliformes: Etmopteridae) from Taiwan.. 29 records from A new species of Jupiaba Zanata, 1997 (Ostariophysi, Characiformes, Characidae) from the rio Tocantins drainage, Brazil.. 191859 records from herbario. 31747 records from Syrphids of Ireland. 36657 records from Plant Specimen from Herbarium (LBG) in China, Lushan Botanical Garden, Jiangxi and Chinese Academy of Sciences. 18405 records from Oregon State Ichthyology Collection. 213534 records from South Australian Museum Australia provider for OZCAM. 372 records from Colección de Entomología - Arthropoda. 1 records from Die Chilopodenfauna Griechenlands. 4 records from Range table from planktonic foraminifers in ODP Hole 172-1061A. 54 records from Range table from planktonic foraminifers in ODP Hole 180-1108B. 38 records from Range table from planktonic foraminifers in ODP Hole 180-1110A. 29248 records from Animal Sound Archive. 18 records from RSPB - Black grouse lek survey in Lothian and Borders, 2008 (RSPB). 1 records from Oribates setosus. 724 records from University of Amsterdam (NL) - Páramo vegetation research, Talamanca Cordillera, Costa Rica. 27927 records from Emporia State University Herbarium. 13 records from Kleinsäuger der Mergelgruben Misburg (Hannover). 77 records from Relatiev abundance of benthic foraminifera in surface sediments of the NW African continental margin (Table 5). 8706 records from Botanical Collection. 8000 records from Crustacean specimen detabase of Kanagawa Prefectural Museum of Natural History. 77 records from (Table 2) Relative abundances of shallow-water foraminifera in ODP Hole 133-821A. 25 records from A new Gymnotus (Teleostei: Gymnotiformes: Gymnotidae) from the Pantanal Matogrossense of Brazil and adjacent drainages: continued documentation of a cryptic fauna.. 1 records from Nothrus doliaris. 4086 records from Inventaire National du Patrimoine Naturel : Espèces Végétales Menacées de France métropolitaine. 125 records from (Appendix I) Foraminifera abundance in DSDP Hole 7-62. 7868 records from Inventaire National du Patrimoine Naturel : Insectes Coléoptères Saproxylophages de France. 36 records from Ecsenius caeruliventris and E. shirleyae, two new species of blenniid fishes from Indonesia, and new distribution records for other species of Ecsenius.. 27207 records from UAM Entomology Observations (Arctos). 4 records from A new species of Pachyurus Agassiz 1831 (Teleostei: Perciformes: Sciaenidae) from the Río Napo basin, Eastern Ecuador.. 118 records from Tab. 6: Relative Abundanz einzelner Arten der Endofauna. 18 records from Spielwiese. 27 records from Vögel. 504 records from Schatzinsel Wangerooge. 91 records from Botanical Society of the British Isles - RISC Botanical Non-Native Species Records . 713 records from (Figure 6) Total organic carbon content and counted dinoflagellate cysts of sediment core GeoB10706-3. 16 records from Beiträge zur Kenntnis der Oribatiden (Acari) Europas III. Suctobelbella alloenasuta n. sp. und Suctobelbella messneri n. sp. sowie die bisher aus der DDR bekannten Arten der nasalis-subtrigona-Gruppe (Suctobelbidae). 91 records from (Table T2) Paleocene calcareous nannofossil abundance of ODP Hole 173-1068A. 360 records from Küstenschutzwald. 74 records from Naturschutzgebiet Lippeaue (Marl) - Pfadis in Sickingmühle. 204 records from Abundance of organic-walled dinoflagellate cysts of sediment core GeoB1710-3. 1 records from Beitrage zur Kenntniss paläarctischer Myriopoden. XV. Aufsatz: Lithobiiden aus Bosnien, Herzogovina und Dalmatien. 1 records from Ctenophora ZMK. 107 records from Biotop Binsenwiesen und Ernst-Reiter-Wiese (Wehrheim/Taunus). 18 records from Schulgarten der Gesamtschule Am Heidberg. 998 records from (Appendix 6) Benthic foraminifera at termination II in sediment core GIK23414-9 in the Norwegian Sea. 171506 records from Bryophyte herbarium, Trondheim (TRH). 94 records from Total foraminifera counts of multinet PO247/2_MSN1389. 97 records from Plasm bearing foraminifera counts of multinet PO247/2_MSN1383. 96 records from Total foraminifera counts of trap L2_92_A42. 315 records from Size of planktic foraminifera at CTD station PS55/030. 3900 records from Dinoflagellate cysts counts of sediment core MD95-2042. 571 records from Cuxhavener Küstenheiden. 851 records from (Figure 2d) Distribution of planktonic foraminifera in bottom sediments of Core Vy20-3245. 491 records from John Muir Trust - Plants, Bryophytes and Lichens recorded on the Nevis Estate during summer 2003.. 326636 records from University of British Columbia Herbarium (UBC) - Vascular Plant Collection. 25 records from Glyptothorax botius (Hamilton, 1822), a valid species of catfish (Teleostei: Sisoridae) from northeast India, with notes on the identity of G. telchitta (Hamilton, 1822).. 66722 records from SANT herbarium vascular plants collection. 688 records from Algae, Norwegian College of Fishery Science. 335 records from (Appendix 6) Benthic foraminifera at termination II in sediment core PS1906-2 in the Greenland Sea. 124 records from Total foraminifera counts of multinet M10/2_MSN232. 135 records from Total foraminifera counts of multinet M21/3_MSN688. 399 records from Distribution of planktic foraminifera (125-250 µm) of sediment core GIK17732-1. 1127 records from Planktic foraminifera counts of sediment core RC14-35. 3 records from Redescription of Platynaspis flavoguttata (Gorham) (Coleoptera, Coccinellidae) and notes on nomenclature of Platynaspis kapuri Chakraborty and Biswas. 96 records from (Table T4) Biogenic and mineral composition of sediments cored in Hamburg-Langenhorn. 210 records from (Table 2) Neogloboquadrina plexus coiling direction at DSDP Site 49-410 and Holes 81-552A, 94-610E, and 94-611C. 25883 records from Monitoring data from the federal state Saxony (Germany). 36 records from Assemblage of living benthic foraminifera in sediment core SO117_MC468, >125 µm fraction. 232 records from Distribution of planktic foraminifera of sediment trap OG5. 120 records from Plasm bearing foraminifera counts from M35/1_MSN1060. 34 records from Foraminifera species abundances from tow TT007_9-MOC18. 3320 records from (Figure 4) Distribution and relative abundances of the benthic foraminifers recovered from the Jurassic section of DSDP Hole 79-547B. 6 records from Review of the genus Metopheltes Uchida, 1932 (Hymenoptera, Ichneumonidae) with description of a new species from Vietnam. 1 records from Nothrus runcinatus. 10 records from Eupolybothrus cavernicolus Komerički & Stoev sp. n. (Chilopoda: Lithobiomorpha: Lithobiidae): the first eukaryotic species description combining transcriptomic, DNA barcoding and micro-CT imaging data. 140 records from (Appendix) Stable carbon and oxygen isotopes, and Mg/Ca ratios of foraminifera from ODP Hole 154-925A. 106 records from (Appendix II) Foraminifera abundance in DSDP Hole 22-214. 325 records from Triebesbach (Zeulenroda-Triebes). 43 records from Gewässeruntersuchung Grötzinger Baggersee. 24 records from Ornithologische Wanderung um Tussenhausen. 101 records from BIRDRACE Enger am Spektiv. 89 records from Total foraminifera counts of multinet M10/2_MSN298. 56 records from Total foraminifera counts of multinet M21/5_MSN741. 233 records from Distribution of planktic foraminifera (125-250 µm) of sediment core GIK23059-3. 22 records from Collection Mantodea - SMF. 41 records from Total foraminifera counts of multinet M21/4_MSN711. 166 records from Plasm bearing foraminifera counts of multinet M21/1_MSN610. 15 records from Plasm bearing foraminifera counts of multinet PO231/3_MSN1330. 21 records from Foraminifera species abundances from tow TT007_15-MOC23. 20 records from Abundance and carbon biomass of phytoplankton at station TT012_5-CTD88. 18 records from Abundance, biovolume and biomass of heterotrophic dinoflagellates at station TT007_15-CTD152. 7 records from Sarcodine counts and carbon biomass at station TT008_5-PMOC2. 3 records from Sarcodine counts and carbon biomass at station TT008_6-PMOC7. 3 records from Sarcodine counts and carbon biomass at station TT007_5-CTD53. 22 records from Phytoplankton abundance at bottle station GOM6/1. 128007 records from UMMZ Mammal Collection. 3219 records from (Appendix Table 2) Absolute abundances of benthic foraminifers in DSDP Site 94-610. 39 records from Pollen profile 1 from Richland Creek. 694 records from Gastropoda, scaphopoda and amphineura abundance of surface sediments of the Atlantic continental shelf off Southern Spanish Sahara, West Africa (Table 2). 58 records from Abundance of living benthic foraminifera in sediment core CD86_04_BC4. 7 records from Assemblage of living benthic foraminifera in sediment core SO117_MC464, 30-63 µm fraction. 98 records from Plasm bearing foraminifera counts of multinet M12/3_MSN561. 96 records from Total foraminifera counts of multinet M27/2_MSN883. 133 records from Planktic foraminifera counts at CTD station PS55/079-1. 43 records from Late Albian Col de Palluel (SE France, Niveau Breistroffer): results from palynomorphs. 36 records from Phytoplankton abundance in surface water in 2000, Ancon, Peru. 32 records from Dorset Environmental Records Centre - Ross Coral Mapping Project - NBN South West Pilot Project Case Studies. 458 records from (Appendix Table 4) Distribution of dead benthic foraminifera in surface sediments. 50 records from Leben in den Elbwiesen. 206 records from Uso y monitoreo de los recursos naturales en el Corredor Biológico Mesoamericano (áreas focales Xpujil-Zoh Laguna y Carrillo Puerto) Herpetofauna. 9 records from Microzooplankton abundance and biomass at station NBP97-03-04-5. 31 records from Meiofauna abundances at the Arctic Håkon Mosby Mud Volcano (HMMV) of sediment core PS64/363-1a. 13 records from Nannofossil abundance of Hole 84-570. 22 records from Nannofossil abundance of Hole 39-355. 4 records from Nannofossil abundance of Hole 55-430A. 3968 records from Antarctic Jellyfish. 184 records from (Table 10) Occurrence of benthic foraminifera in ODP Hole 112-688A. 4277 records from Fundación Carl Faust: Herbario del Jardí Botànic Marimurtra: HMIM. 243 records from Grand Manan Basin Benthos (OBIS Canada). 18155 records from Algae Collection of National Museum of Nature and Science. 44 records from Leegmoor (Moormerland/Leer). 14 records from Large protozoa abundance measured on concentrated water bottle samples at station PS58/090-2. 1308 records from Dinoflagellate cysts counts of sediment core MD95-2010. 6 records from Microzooplankton abundance and biomass at station NBP97-08-31-7. 1278 records from (Appendix 2-6) Distribution of planktonic foraminifera in late Neogene sediments of DSDP Site 58-445 in the western Pacific Ocean. 1677 records from Distribution of planktonic foraminifera in DSDP Hole 31-296 (Table III). 5 records from Abundance of radiolaria at station LV28-66-1. 69 records from Naturpark Kottenforst-Ville 17.6.09. 63 records from Nannofossil abundance of Hole 7-62A. 2 records from Nannofossil abundance of Hole 25-249. 8 records from Nannofossil abundance of Hole 49-412A. 4 records from Abundance of broken diatom frustules measured on water bottle samples at station PS58/009-2. 39835 records from Lichen herbarium, Trondheim (TRH). 150 records from Phytoplankton abundance at station CD47_0306C#7. 101 records from Nannofossil abundance of Hole 4-30. 4804 records from North Ayrshire Countryside Ranger Service - Species within North Ayrshire from 1984 - Present. 21 records from Meiofauna abundance in sediment core 12930-018. 19 records from Bayerische Donau - Großmehring. 22857 records from National Botanic Garden Belgium - Myxomycetes. 48 records from Crustacea in surface sediments off Sylt collected during Heincke cruise HE275. 69 records from (Table 3c) Distribution of planktonic foraminiferal tests in sediments from Core NKA-40T. 238 records from Elaboración de fichas de 5 especies de lacertilios: PROY-NOM-059-ECOL-2000. 6912 records from Bryophyte Collection of Natural History Museum and Institute, Chiba. 2750 records from Botanical specimens database of Mr. Jiro Ito collection, Shizuoka Prefecture Museum of Natural History. 1 records from Heckenstreifen am Zehntbergweg. 20 records from Benthic macrofauna abundance of sediment core 12930-039. 11 records from (Table 4) Abundance of Pulleniatina obliquiloculata in sediment core ERDC-129BX. 1180 records from Planktic foraminifera counts of sediment core V29-174. 196 records from Artenvielfalt rund um die Dalbek-Schule. 2588 records from Marchantiophyta / Hepatics / Liverworts of Russian Fennoscandia. 936 records from (Figure 6) Range chart of dinocysts of ODP Hole 104-642C. 249 records from (Table 2) Distribution of calcareous nannofossils from selected samples of ODP Hole 107-652A. 9 records from Component analysis of TV-guided grab sampler GeoB10071-5. 7 records from (Table 3+4) Abundance, biomass, production, and grazing of prokaryotes, nanoflagellates, ciliates, and dinoflagellates in three areas close to the Antarctic Peninsula in spring and summer 1995/96. 218 records from Distribution of main calcareous nannofossils at Site 1093. 195 records from Lower Albian Mazagan Plateau (Oceanic Anoxic station 1b) ecological important nannofossils and stable isotopes, DSDP Site 545. 33 records from Coccolith counts of multinet M32/5_MSN977. 2 records from Nannofossil abundance of Hole 3-18. 7 records from Nannofossil abundance of Hole 27-259. 2 records from Nannofossil abundance of Hole 14-136. 1298 records from Colección de Aves y Mamíferos del Valle de Cuatrociénegas, Coah., México (UANL). 26 records from (Table 4) Mean values of the chemical data from the ash layers from ODP Legs 113 and 114. 688 records from Banco de información sobre características tecnológicas de maderas mexicanas. 7791 records from Base de datos de las gramíneas (Poaceae) del noreste de México. 1320 records from Percentages of planktonic foraminifera species in sediment core RC24-27. 1000 records from Diplopoda (JJHA-DI). 9494 records from Colección de plantas vasculares del Herbario "Jaime Andrés Rodríguez". LEB. 1 records from (Table 1.2.1.1) Abundance of sympagic meiofauna of sea-ice core PS69/567-1. 1020 records from (Table 3) Distribution of planktonic foraminifers in ODP Site 126-791. 358 records from Myriapoda - SMF. 10 records from (Table 2) Abundance and biomass of the main phytoplankton groups in subsurface water samples collected in the southeastern Barents Sea in April 2000. 507 records from Planktic foraminifera counts during POLARSTERN cruise ARK-XIII/2. 2 records from Apectodinium spp. and percentage of endemic and bipolar dinoflagellate cysts of ODP Hole 182-1128D. 455 records from (Table 3) Occurrence of benthic foraminifers in ODP Hole 116-718C. 69 records from (Table 7) Distribution of Maestrichtian to late Campanian nannofossils in ODP Hole 108-661A. 945 records from (Table 7) Distribution of planktonic foraminifers in ODP Hole 108-660A. 501 records from EcoRecord - Mayfly (Ephemeroptera) records held by EcoRecord for the Birmingham and the Black Country area collated prior to March 2013. 32 records from (Table 2) Distribution of ice-rafted fossils in ODP Hole 104-643A. 8 records from (Table 2.2.1.1) Abundance of sympagic meiofauna of sea-ice core IO-3. 132 records from Cretaceous ostracods of DSDP Hole 10-95 (Figure 2). 828 records from Phytoplankton abundance during Professor Vodyanitskiy cruise PV13. 635 records from Bermuda Atlantic Time-series Study Zooplankton Census. 81889 records from Coleoptera collection, Natural History Museum, University of Oslo. 287 records from Collection Odonata - SMF. 88335 records from Canadian Museum of Nature Bird Collection. 54138 records from Flora Mycologica Iberica. 36169 records from Herbarium of Vascular Plants Collection of the University of Extremadura (Spain). 755529 records from Inventaire National du Patrimoine Naturel : Oiseaux hivernants de France. 6450 records from Meiobenthos of subtidal sandbanks on the Belgian Continental Shelf (EurOBIS). 479 records from CBS Bacteria Database. 9647 records from Epiphytic Lichens of G. Lettau at the Botanical Museum Berlin-Dahlem. 9858 records from Planktic foraminifera distribution on sediment core GIK17957-2. 1611 records from Percentages of planktonic foraminifera species in sediment core RC13-189. 1656 records from Relative abundance of planktic foraminifera in the 120 kyr time slice reconstruction of sediment core RC11-86. 3 records from Occurrence of mammalia relicts at site Sesselfelsgrotte. 769 records from (Table 5) Planktonic foraminifer abundance of ODP Hole 162-982A. 238 records from Range table from dinoflagellates, acritarchs and prasinophytes in ODP Hole 160-967A. 11370 records from Distribution of planktic foraminifers of core V22-174. 157 records from Microplankton abundance in the euphotic zone of the Aegean, Levantine and Ionian Seas in March-April 1987. 1 records from Occurrence of mammalia relicts at site Egtved. 7 records from Planktic foraminifera abundance of Hole 53-418B. 420 records from Planktic foraminifera abundance of Hole 33-318. 8 records from Range table from planktonic foraminifers in ODP Hole 172-1057A. 19 records from Microfossil abundance of Hole 59-451. 14 records from Microfossil abundance of Hole 29-277. 127133 records from Fish specimens. 11 records from IPK Genebank. 7723 records from NCOS1959_Echinodermata (OBIS China). 57 records from Planktic foraminifera assemblage in sediment core GIK23055-2. 602 records from NABU-Projekt (Osterode am Harz) Südharzer Gipskarst. 105 records from Occurrence of mammalia relicts at site l´Abri du Pont d´Ambon. 35 records from Range table from planktonic foraminifers in ODP Hole 144-873A. 973 records from Range table from planktonic foraminifers in ODP Hole 157-954B. 32 records from (Table 2) Planktonic foraminifer abundance of ODP Hole 162-907B. 75 records from Wiese und Bach am Kleinen Eutiner See (Eutin). 2178 records from Flora exsiccata Bavarica. 6644 records from The Myxomycetes Collections at the Botanische Staatssammlung München - Main Collection. 184 records from "Tre Pini" (Montebelluna, Italien). 88 records from Teich Berlin Wuhlheide. 22 records from Microplankton abundance at Station SEPT-1997-GN36199704605MSB03 in the euphotic zone of the Aegean Sea in September 1997. Part 3 - coccolithophores and other groups. 22 records from Occurrence of mammalia relicts at site Igrita Cave. 13 records from Planktic foraminifera abundance of Hole 47-398A. 215 records from Foraminifera abundance of Hole 64-480. 840 records from Range table from planktonic foraminifers in ODP Hole 155-944A. 366 records from (Table 3) Planktonic foraminifer abundance of ODP Hole 162-980A. 507 records from Hongos hyphomycetes de áreas tropicales y semitropicales del Estado de Veracruz. 243 records from Memorial University Department of Biology Collection. 6627 records from ATCC Fungi Collection Catalog. 433463 records from Israel Nature and Parks Authority. 4554 records from Planktic foraminifera counts (census) of sediment core MD96-2080. 4 records from Pycnogonida collection of National Museum of Nature and Science. 177494 records from Primer censo de plantas leñosas de una Parcela Permanente de 25 hectáreas, ubicada en la Reserva Natural La Planada (Nariño, Colombia). 522 records from Relative abundance of planktonic foraminifera in sediment core L-198. 79 records from Umgebung von Schorndorf. 536 records from Walldorf-Wiesloch: "Natur über den Gleisen". 32 records from Microplankton abundance at Station MARCH-1997-GN36199704603MNB03 in the euphotic zone of the Aegean Sea in spring 1997. Part 3 - coccolithophores and other groups. 17 records from Benthic foraminifera abundance of Hole 11-108. 173 records from A taxonomic review of the genus Myrmelachista (Hymenoptera: Formicidae) in Costa Rica.. 41 records from Occurrence of mammalia relicts at site la Grotte des Eglises. 563 records from Foraminifera abundance of Hole 74-526A. 484 records from Planktic foraminifera abundance of Hole 60-456A. 55 records from Range table from planktonic foraminifers in ODP Hole 170-1039C. 10 records from Results of foraminifer and ostracode analyses of Hole 302-M0002A. 45 records from Parcela Permanente en el Pantano Martos. 1 records from Oribates fuscipes. 57 records from Langes Tannen in Uetersen. 161 records from Microplankton abundance at Station SEPT-1997-GN36199704605MSB06 in the euphotic zone of the Aegean Sea in September 1997. Part 2 - dinoflagellates. 120 records from Planktic foraminifera abundance of Hole 7-62. 230 records from Planktic foraminifera abundance of Hole 84-569. 4730 records from Range table from planktonic foraminifers in ODP Hole 152-918A. 666 records from Range table from dinoflagellates, acritarchs and prasinophytes in ODP Hole 151-908A. 616 records from Phytoplankton long-term time-series at the fixed coastal station in the Gulf of Naples, data for the years 2000-2004. Part 3. 332 records from Forster herbarium, Göttingen (GOET). 17 records from Microplankton abundance at Station SEPT-1997-GN36199704606MNB02 in the euphotic zone of the Aegean Sea in September 1997. Part 3 - coccolithophores and other groups. 84 records from Occurrence of mammalia relicts at site Sütto_6. 1 records from Occurrence of mammalia relicts at site Raagelund. 341 records from Neogene palynomorpha from site 81-552. 46 records from Planktic foraminifera abundance of Hole 6-44. 1059 records from Planktic foraminifera abundance of Hole 15-148. 147 records from Planktic foraminifera abundance of Hole 22-217. 201 records from Planktic foraminifera abundance of Hole 11-103. 4842 records from (Table 6) Planktonic foraminifer abundance of ODP Hole 162-982B. 12 records from Range table from planktonic foraminifers in ODP Hole 178-1096A. 12 records from Range table from planktonic foraminifers in ODP Hole 182-1133A. 1148 records from (Fig. 7) Distribution of dinoflagellate cysts in Early Cretaceous sediments of DSDP Hole 43-387 in the North Atlantic. 30 records from Range table from benthic foraminifers in ODP Hole 181-1119C. 1578995 records from Inventaire National du Patrimoine Naturel : Flore Franco-Belge. 4021 records from (Figure 7) Distribution of benthic foraminifers in the Oligocene to upper Miocene DSDP of Hole 71-513A. 23 records from Benthic foraminifera abundance of Hole 93-603. 34 records from Benthic foraminifera abundance of Hole 42-381. 5 records from Range table from benthic foraminifers in ODP Hole 181-1120C. 1 records from Die Myriopodenfauna von Albanien und Jugoslavien. 3 records from Dinoflagellate abundance of Hole 14-136. 816 records from Phytoplankton abundance in surface water in February 1998, Ilo, Peru. 1 records from Cheiloneurus flaccus (Walker, 1847) (Hymenoptera: Encyrtidae), new to New Zealand. 1167 records from Birds (KNAM-BI). 130737 records from Ground Beetle Recording Scheme - Carabid data for Great Britain from the Ground Beetle Recording Scheme held by BRC. 24660 records from The DNA and Sample Repository at AIT. 1 records from Oribates humeralis. 3038 records from Museu Paraense Emilio Goeldi - Lepidoptera Collection. 2146 records from William Nylander lichen collection. 1 records from Nothrus sordidus. 38 records from Northern Ireland European hare (Lepus europaeus) survey 2005. 6848 records from Ratti Master Thesis / Fraser Valley, British Columbia. 26 records from Microfossil abundance of Hole 39-356. 12 records from Phytoplankton abundance in surface water in October 1995, Ilo, Peru. 192 records from Phytoplankton abundance in surface water in August 1997, Pisco, Peru. 782 records from Joint Nature Conservation Committee - Otters: Northern Ireland Otter Survey Database. 31 records from Description of Cathorops mapale, a new species of sea catfish (Siluriformes: Ariidae) from the Colombian Caribbean, based on morphological and mitochondrial evidence.. 274 records from Detection histories for eight species of Amazona parrots in Venezuela during the NeoMaps bird surveys in 2010. 12555 records from Natural History Museum Rotterdam (NL) - Plantae collection. 1462 records from Biological Records Centre - Dixidae (Diptera) records from Britain and Ireland to 1988. 3 records from Mammalia (SMNH-MM). 123006 records from Finnish Entomological Database: Diptera. 92 records from (Figure 1) Stratigraphic distribution of taxa at DSDP Hole 79-547B. 19 records from (Table 1) Rodent (lemming and vole) densities in 5 study areas in the Canadian Arctic. 59 records from Main components of radiolarian assemblage at Site 177-1092. 159 records from (Table 1) Distribution of benthic foraminifera in surface sediment of the Elbe estuary. 8097 records from tef-database. 1 records from Nothrus rostratus. 6 records from New country records of reptiles from Laos. 70 records from Instituto Nacional de Pesquisas da Amazônia - Porifera Collection. 5452 records from Systematic census of the private plantations of the firewood of the Benin .. 202 records from Uncorrected Mg/Ca and sea surface temperature data for Site 165-1000. 103 records from BIRDRACE federleser. 109 records from BIRDRACE Die Borner. 177 records from Benthic macrofauna abundance and biomass in surface sediment during cruise PLG95A. 859 records from Royal Horticultural Society - RHS berberis sawfly (Arge berberidis) monitoring . 777 records from (Fig. 3) Raw counts and stratigraphic ranges of selected dinoflagellate cyst and acritarch taxa in ODP Hole 151-907A. 264 records from Terrestrial Heteroptera Recording Scheme (Shieldbugs & allied species) - RISC Heteroptera Non-Native Species Records . 1 records from Pelops fuligineus. 32297 records from Invertebrata Collection of Institute of Systematics and Evolution of Animals. 220318 records from UF FLMNH Ichthyology. 4685 records from Registros biológicos de especies de fauna vertebrada terrestre en las centrales de San Carlos y Jaguas - 2006. 4873 records from Berkshire Reptile and Amphibian Group - BRAG - Berkshire Reptile and Amphibian Records . 13 records from (Table 2b) Species of planktonic foraminifera found in surface layer bottom sediment at Station Vy20-3217GR. 72 records from Birdrace-Buteo2DO-Dortmund. 70 records from Gewässer des Wartbergparks Stuttgart (bei der Ökostation der VHS Stuttgart). 16 records from Naturschutzgebiet "Gellener Torfmöörte" (Landkreis Wesermarsch). 3268 records from Royal Horticultural Society - RHS rosemary beetle (Chrysolina americana) monitoring. . 19 records from A new species of Anabarhynchus (Diptera: Therevidae) from an ocean beach in south east Victoria. 9161 records from Palaeobiology - Vertebrate Comparative Osteology Collection - Royal Ontario Museum. 50 records from Phytoplankton abundance in the wadden sea off List, Sylt, North Sea in 2006. 20755 records from pins. 129 records from (Table T3) Calcareous nannofossil stratigraphy of ODP Hole 198-1208A. 6239 records from (Figure 1) Distribution of dinoflagellate cysts in the mid-Cretaceous of DSDP Hole 79-545. 19237 records from Alterra (NL) - Biological Indicator Soil Quality-Microarthropods inventory in different habitats. 128787 records from Seed and Leaf Beetle Recording Scheme - Bruchid and Chrysomelid Distributions in Britain and Ireland: pre 1900, 1900-1979, 1980 onwards. 4312 records from (Table 18) Benthic foraminifera in late Miocene sediments of DSDP Hole 90-593. 1250 records from Plant Observation Records of Japan. 47 records from Taxonomic status of the Guadalupe Darter, Percina apristis (Teleostei: Percidae).. 32681 records from Ground Beetle of Japan Specimen Database. 20 records from Heteroptera - SMNG. 60710 records from Leicestershire and Rutland Environmental Records Centre - Leicestershire & Rutland Coleoptera. 2576 records from Hosted Invertebrate Collection 01. 1023 records from Greater Manchester Ecology Unit - Invasive and Non-native Species From Greater Manchester . 171 records from Biodiv-Camp Sandmagerrasen in Nürnberg/Langwasser. 15 records from Beisetal bei Niederbeisheim. 84 records from BIRDRACE Avinauten. 1904 records from Terrestrial Heteroptera Recording Scheme (Shieldbugs & allied species) - Flickr (01) Shieldbugs & allied species. 273 records from Fossil occurrence from planktonic foraminiferas from IODP Hole 322-C0012A. 2513 records from Carabidae of the Tatra Mts.. 1 records from Zetes ephippiatus. 8 records from Torpedo formosa sp. nov., a new species of electric ray (Chondrichthyes: Torpediniformes: Torpedinidae) from Taiwan.. 60 records from The genera of the Neotropical armored catfish subfamily Loricariinae (Siluriformes: Loricariidae): a practical key and synopsis.. 3 records from Beitrage zur Kenntniss paläarctischer Myriopoden. XV. Aufsatz: Lithobiiden aus Bosnien, Herzogovina und Dalmatien. 5 records from Fledermäuse u. nachtaktive Insekten. 104 records from BIRDRACE Die Marburger-Vogelwelt.de radelt. 61 records from (Table 1) Sedimentology of core D11957P. 56 records from Assemblage of living benthic foraminifera in sediment core SO118_MC-52, 30-63 µm fraction. 203945 records from Joint Nature Conservation Committee - Marine benthic dataset (version 1) commissioned by UKOOA. 3 records from Selenops muehlmannorum spec. nov. from Southern Laos (Araneae: Selenopidae). 1197 records from North Atlantic (Rockall Plateau) coccolith assemblage data for MIS 5 of ODP Hole 162-980B. 24694 records from Amphibian Specimens. 2234 records from (Figure 1) Dinoflagellate cyst stratigraphy of DSDP Hole 80-548A. 9948 records from Bees of Canada / Gschwendtner property collection. 149 records from BIRDRACE Birding Bentheim. 49 records from Total foraminifera counts of multinet M10/2_MSN234. 124 records from Total foraminifera counts of multinet M10/2_MSN317. 28 records from Content of coarse fraction and G. menardii in sediment corev V25-59. 6 records from Microzooplankton abundance and biomass at station NBP97-08-07-1. 34 records from Microzooplankton abundance measured on water bottle samples at station PS65/424-3. 30 records from Microzooplankton abundance measured on water bottle samples at station PS65/553-3. 2 records from Nannofossil abundance of Hole 9-82. 69 records from (Table 11) Distribution of coccoliths along Core AMK7-786 from the Tajura Rift. 282 records from Migratory shorebirds (sandpipers and plovers) in Hokkaido. 246 records from CaCO3, biogenic opal, TOC, and microfossil observations of sediment core MR06-04_PC23A. 855 records from (Table 1) Distribution of ostracods in Jurassic sediments of DSDP Hole 79-547. 761 records from Dorset Environmental Records Centre - Dorset Heath - NBN South West Pilot Project Case Studies. 2816 records from Araneae collection (AR) of the Muséum national d'Histoire naturelle (MNHN - Paris). 84 records from Roter Berg Werdau (Leubnitz). 52 records from Naturschutzstation Weinberghaus (Dessau). 76 records from BIRDRACE Nachtigallen. 108 records from Plasm bearing foraminifera counts from M35/1_MSN1065. 24 records from Content of coarse fraction and G. menardii in sediment corev V25-43. 46 records from An der Ohm, (Wettsaasen). 56 records from Zitadelle Berlin-Spandau (7b). 149 records from Wirbach. 23 records from Wiese Niederaula. 31 records from Blumenwiese und Heckensaum , Kornberg (Gruibingen). 89 records from BIRDRACE Hasenclevers Erben - NaBu-Bi-BirdRace-Open. 95 records from BIRDRACE BiBi. 17 records from Feuchtwiese am Nationalpark-Haus Neuwerk. 11 records from Plasm bearing foraminifera counts from multinet M31/2_MSN896. 45 records from Plasm bearing foraminifera counts from multinet SO119_MSN1286. 6883 records from Kingfisher Survey 2010. 49 records from Plasm bearing foraminifera counts of multinet M26/1_MSN845. 205 records from Total foraminifera counts of multinet M6/7_MSN119. 179 records from Total foraminifera counts of multinet M21/2_MSN657. 202 records from Total foraminifera counts of multinet M6/7_MSN96. 277 records from Distribution of planktic foraminifera (250-500 µm) of sediment core PS1244-2. 60 records from Microzooplankton (larger protists and small copepods) abundance measured on concentrated water bottle samples at station PS65/543-5. 27 records from Pollen profile from Muscotah Marsh B. 96 records from Assemblage of total living benthic foraminifera in sediment core SO118_MC-51. 44245 records from Cumbria Biodiversity Data Centre - Cumbria Biodiversity Data Centre. Vertebrate Observation Records, other than Birds. Pre-2010 for Cumbria . 141 records from Benthic foraminiferal assemblage (Rose Bengal stained) in MUC SC2-L, size fraction >150 µm. 26 records from Assemblage of living benthic foraminifera in sediment core CD146_55901#11, >150 µm. 49 records from Total foraminifera counts of multinet M10/2_MSN238. 48 records from Diatom assamblage in samples from sediment trap OG5. 1811 records from Western Palaearctic Ectoedemia (Zimmermannia) Hering and Ectoedemia Busck s. str. (Lepidoptera: Nepticulidae): five new species and new data on distribution, hostplants and recognition. 39 records from Ostracoda abundance of Hole 24-238. 4 records from Range table from ostracoda in ODP Hole 159-960A. 13 records from Diatom abundance measured on water bottle samples at station PS58/042-2. 1240 records from Diversidad y conservación de orquídeas de la región de Chimalapa, Oaxaca, México. 288 records from (Appendix 6) Benthic foraminifera at termination II in sediment core GIK23256-1 in the Arctic Ocean. 102 records from Plasm bearing foraminifera counts of multinet M12/3_MSN559. 137 records from Total foraminifera counts of multinet M21/3_MSN661. 73 records from Plasm bearing foraminifera counts of multinet M36/6_MSN1196. 164 records from Planktic foraminifera counts at CTD station PS55/066. 38 records from Phytoplankton abundance during ARGOS cruise Argos90/8. 74 records from Abundance of Lanice in 2007-03 from an experiment in the Wadden Sea off List, Sylt. 69 records from (Table T6) Calcareous nannofossil stratigraphy of ODP Hole 198-1210A. 180 records from Assemblage of living benthic foraminifera in sediment core GeoB3701-1. 18 records from Phytoplankton abundance in surface water in 1995, Ancon, Peru. 668 records from Phytoplankton abundance during OCEANIA cruise Oceania90. 12 records from Abundance of radiolaria at station LV28-44-1. 258 records from Upper Aptian Pré-Guittard (Niveau Kilian) ecological important nannofossils, stable isotopes, carbonate and TOC values in SE France. 18 records from Benthic macrofauna abundance of sediment core 13200-075. 2349 records from (Appendix B) Stratigraphic range and relative abundance of Neogene planktonic foraminifer taxa in ODP Hole 120-748B. 254 records from Grünes Germersheim. 845 records from Planktic foraminiferal assemblages of the Paleocene-Eocene Thermal Maximum from ODP Hole 198-1209B, Shatsky Rise, Pacific Ocean. 23 records from Abundance and carbon biomass of phytoplankton at station TT008_5-CTD39. 8 records from Microplankton counts and carbon biomass at station TT012_5-CTD10. 6 records from Nano and microzooplankton abundance and biomass at station NBP96-04A-13-4. 12 records from Phytoplankton abundance in surface water in 2004, Ancon, Peru. 11 records from Phytoplankton abundance at station Rigel_2_2005-03 in March 2005, Chipana, Chile. 7 records from Phytoplankton abundance at station Rigel_4_2005-07 in July 2005, Chipana, Chile. 17 records from Nematode genera abundances at the Arctic Håkon Mosby Mud Volcano (HMMV) of sediment core PS64/324-1. 4 records from (Table 3) Contusotruncana contusa morphotypes in DSDP Hole 43-384. 46 records from Aktion Wiese und Wegrain Gitzenheide. 15382 records from Bird Specimens in the Museum of Nature and Human Activities, Hyogo, Japan. 411 records from Coccolith percentage of surface sediment samples. 237 records from Collection Mammalogie - SNSD. 517 records from (Appendix B Table 2) Abundance of organic-walled dinoflagellate cysts of sediment core GeoB2204-2. 1 records from Microzooplankton abundance and biomass at station TT050_26-18. 3 records from (Table T2) Dinoflagellate cyst occurrence in neogene sediments of ODP Hole 178-1096B. 6 records from Nano and microzooplankton abundance and biomass at station NBP97-01-07-5. 34 records from Relative abundance of coccosphere-units of sediment core GIK23071-3. 1942 records from Spiders of Ireland. 3 records from Nannofossil abundance of Hole 1-7. 7 records from Nannofossil abundance of Hole 9-82. 84 records from (Table 2) Distribution of nannofossils in DSDP Hole 87-583. 33 records from Nannofossil abundance of Hole 55-433. 596 records from Planktic foraminifera counts of sediment core A15-558. 51 records from Antarctic Marine Bacteria from Denmark University. 31 records from (Table 8) Relative abundance of benthic foraminifera in ODP Hole 112-682A, Part III. 590 records from Planktic foraminifera assemblage in sediment core SU90-I08. 60351 records from Flora d'Andorra. 185 records from Epi-endofauna abundance in 2007-03 from an experiment in the Wadden Sea off List, Sylt. 4 records from Zwischen Enz und Schule. 102 records from Listhof und Umgebung. 545 records from Distribution of ostracoda in the Arctic Ocean (Table 1). 81 records from Nannofossil abundance of Hole 74-527. 6 records from Phytoplankton abundance at station Rigel_3_2005-07 in July 2005, Chipana, Chile. 1565 records from (Table 1) Calcareous nannofossil distribution at ODP Site 180-1109 from the Solomon Sea, western Pacific. 63 records from Matter enrichment of the macrofauna community of MAC station 12930-005. 4 records from (Table 1) Properties of grab sampled sediments from the Nha Trang Bay. 7 records from A revision of the Aphaenogaster phalangium complex (Hymenoptera: Formicidae: Myrmicinae).. 2 records from (Table 2.2.1.1) Abundance of sympagic meiofauna of sea-ice core IO-5. 108 records from (Table 2b) Species compositioon of planktonic foraminiferas in bottom sediments from Core DM-M-2. 39 records from Heavy minerals of sediment core PS2718-6. 3998 records from Diversidad vegetal en un gradiente en la Sierra Madre Occidental: flora y vegetación de la Región de San Javier y Yécora, Sonora. 20 records from Nannofossil abundance of Hole 7-63A. 4 records from Abundance of broken diatom frustules measured on water bottle samples at station PS58/061-3. 703 records from Planktic foraminifera counts of sediment core V25-59. 418 records from Fossil (GNHM-FO). 775 records from Insect (GNHM-IN). 350 records from (Table 4) Abundance of planktonic foraminifera in ODP Hole 113-690C, small size fraction. 46 records from (Table 1) Distribution of planktic foraminifera in sediments from Core AMK4-410GC. 65066 records from Formación de una base de datos y elaboración de un atlas de la herpetofauna de México. 500 records from Plant Specimens of Oiso Municipal Museum. 40923 records from Naturkundemuseum im Ottoneum Kassel, Entomological Collection. 8 records from Nannofossil abundance of Hole 49-409. 2 records from Abundance of broken diatom frustules measured on water bottle samples at station PS58/012-5. 629 records from Macrobenthos in surface sediments off Sylt collected during Heincke cruise HE241. 1584 records from (Table 2) Distribution of planktonic foraminifers in ODP Site 112-681. 17 records from (Table 3) Stratigraphic distribution of silicoflaggelates, ebridians and actiniscidians in upper Pliocene to Pleistocene sediments of ODP Hole 104-644A. 175 records from (Table 6) Dinoflagellate cyst species distribution in ODP Hole 112-679D. 48 records from Benthic foraminifera and algae abundance of Hole 35-325. 15 records from Benthic macrofauna abundance of sediment core 13077-093. 64 records from Planktic foraminifera counts of sediment core RC13-152. 1192 records from (Table 1) Relative abundances of benthic foraminifera in ODP Hole 117-725C. 480 records from Distribution of Cretaceous and early Danian planktonic foraminifera in ODP Hole 119-738C (Table 1). 58 records from Collection Cnidaria - ZIM Hamburg. 13 records from (Table 2.2.1.1) Abundance of sympagic meiofauna of sea-ice core IO-9. 2300 records from (App 8) Relative contents of planktonic foraminifera species in sediments from Core GeoB3011-2. 10500 records from Formación del banco de datos del herbario (UCAM). 1394 records from Avifauna de la Isla de Cozumel, Quintana Roo_1. 5202 records from Fungi on beech (Fagus sylvatica) wood, Halland, Sweden. 127499 records from Southern Ocean Continuous Zooplankton Recorder (SO-CPR) Survey. 22367 records from Bird Collection. 36 records from (Table 2) Ostracode distribution in ODP Hole 122-760B. 1470 records from (Table 10) Distribution of planktonic foraminifers in ODP Hole 108-662A. 1854 records from Distribución geográfica de las aves y los mamíferos de las zonas montanas de los estados de San Luis Potosí e Hidalgo circundantes de la Sierra Gorda. 213729 records from UAM Entomology Collection (Arctos). 2106 records from (Table 17) Ranges of benthic foraminifers through the late Neogene in ODP Hole 115-713A. 18 records from (Table 4) Distribution of middle Eocene calcareous nannofossils in ODP Hole 149-897D. 15328 records from SOMBASE. 83094 records from Mammal specimens. 2430 records from (Table 2) Distribution of planktic foraminifers of sediment core D11957P. 4660 records from Distribution of planktonic foraminifera of site GeoB1105. 7 records from Pollen profile III at Krumbach. 245 records from (Table 3g) Foraminiferal distribution chart of petroleum well Swan-3. 370 records from (Appendix A) Calcium carbonate concentrations and accumulation rates of ODP Hole 115-710A. 51438 records from Dinoflagelados y Diatomeas del Pacífico tropical mexicano. 38 records from (Table 1) Chiasmolithus species and intermediate forms of ODP Holes 105-647A and 120-748B. 1615 records from (Table 12) Ranges of benthic foraminifers through the Miocene in ODP Hole 115-707A. 10189 records from Royal Museum of Central Africa - Metafro-Infosys - Xylarium. 39835 records from Jardín Botánico de Córdoba: Herbarium COA. 125272 records from Atlantic Reference Centre (OBIS Canada). 42504 records from Fish specimens of Fisheries Research Laboratory Mie University. 2911 records from Distribution of foraminifera of sediment core GeoB1112-4. 1289 records from Percentages of planktonic foraminifera species in sediment core V22-222. 6888 records from WNMU Mammal Collection (Arctos). 15 records from Benthic foraminifera abundance of Hole 56-434B. 1239 records from (Table 1) Neogene benthic foraminifers of ODP Hole 120-747A. 2622 records from (Table 3) Distribution of planktonic foraminifera in the early Cretaceous and early Eocene to late Oligocene sections of ODP Hole 149-897C. 2016 records from Fish tissues, Division of Genomic Resources, UNM, Albuquerque, NM.. 6 records from Desmidiaceae Rostock. 4485 records from Distribution of planktic foraminifers of core RC13-110. 861 records from (Table 1) Percentage of Coccolithus pelagicus vs. Reticulofenestra spp. of ODP Hole 120-747A. 15 records from Description of lithologic section units of IODP Hole 325-M0032A. 87678 records from Herp specimens. 23072 records from Database Schema for UC Davis Wildlife museum. 940 records from Planktic foraminifera distribution of sediment core CS72-37. 116 records from Occurrence of mammalia relicts at site l´Abri de la Ferrassie. 241 records from Planktic foraminifera abundance of Hole 67-499B. 10 records from Range table from planktonic foraminifers in ODP Hole 182-1128D. 28 records from Stadtpark Prinzengarten (Sigmaringen). 53 records from Fonoteca Zoológica, Museo Nacional de Ciencias Naturales, Madrid: FZ_REPTILIA. 599 records from Gerald Hilchie Collection. 5593 records from UCD BOTANICAL CONSERVATORY. 1 records from ZFMK Hymenoptera collection. 1212 records from Foraminifera abundance of Hole 75-532B. 749 records from Planktic foraminifera abundance of Hole 15-154A. 13 records from Planktic foraminifera abundance of Hole 54-425. 50 records from Planktic foraminifera abundance of Hole 60-457. 1251 records from (Figure 5) Foraminiferal abundance and sea surface temperature of sediment core MD95-2011. 4044 records from Cactáceas Columnares de México (IE-MORELIA, UNAM). 294 records from Naturgarten Langenholtensen. 11 records from Microplankton abundance in the euphotic zone of the Aegean Sea at Station SEPT-1998-IR50. 4 records from Microplankton abundance in the euphotic zone of the Aegean Sea at Station JUNE-1998-MNB6. 20 records from Occurrence of mammalia relicts at site le Roc de Marcamps. 6 records from Occurrence of mammalia relicts at site Mitoc Malul Galben. 104 records from Planktic foraminifera abundance of Hole 28-265. 179 records from Planktic foraminifera abundance of Hole 68-502B. 43 records from Dinoflagellate abundance of Hole 14-137. 36 records from UC Davis Department of Anthropology Museum. 208 records from Microplankton abundance at Station SEPT-1997-GN36199704605MSB02 in the euphotic zone of the Aegean Sea in September 1997. Part 2 - dinoflagellates. 27 records from Microplankton abundance at Station MARCH-1998-GN36199804611MNB03 in the euphotic zone of the Aegean Sea in March 1998. Part 3 - coccolithophores and other groups. 91 records from Range table from planktonic foraminifers in ODP Hole 175-1076A. 18 records from Range table from benthic foraminifers in ODP Hole 144-871B. 71 records from Range table from benthic foraminifers in ODP Hole 171-1052A. 73 records from Phytoplankton abundance in surface water in January 1996, Chimbote, Peru. 86 records from Microplankton abundance in the euphotic zone of the Aegean and Levantine Seas in August-Sepmember 1989. 20 records from Microplankton abundance in the euphotic zone of the Cretan Sea at Station MARCH-1995-D4. 8 records from Microplankton abundance in the euphotic zone of the Aegean Sea at Station SEPT-1998-IR64. 99 records from Occurrence of mammalia relicts at site l´Abri de Combe-Cullier. 331 records from Range table from planktonic foraminifers in ODP Hole 141-859A. 399 records from Range table from planktonic foraminifers in ODP Hole 155-937B. 395 records from Range table from planktonic foraminifers in ODP Hole 180-1118A. 15 records from Range table from planktonic foraminifers in ODP Hole 192-1187A. 501 records from Range table from benthic foraminifers in ODP Hole 189-1169A. 44 records from Planktic foraminifera abundance of Hole 51-417A. 18 records from Planktic foraminifera abundance of Hole 94-611E. 385 records from Benthic foraminifera abundance of Hole 76-533. 4 records from Dinoflagellates, pollen and spore abundance of Hole 29-282. 19610 records from Colección del Departamento de Biología Animal (Zoología) de la Universidad de La Laguna. 2326 records from Jardín Botánico Atlántico, Gijón: JBAG. 1 records from Hoplophora longula. 12 records from A new North American species of Pogonomyrmex (Hymenoptera: Formicidae) from the Mohave desert of Eastern California and Western Nevada.. 38 records from Notizen über Oribatei (Acari). II. 2476 records from Range table from benthic foraminifers in ODP Hole 154-929A. 198 records from Phytoplankton abundance in surface water in January 1996, Pisco, Peru. 2737 records from Gunma Museum of Natural History, Molluscan Specimen. 34140 records from Museo Nacional de Ciencias Naturales, Madrid: MNCN_Herpeto. 84 records from Calcareous dinoflagellate cysts of multicorer M51/3_562-5, grain fraction < 20µm. 5363 records from Colección Ornitológica de la Universidad del Valle. 25 records from Benthic foraminifera abundance of Hole 1-4. 881 records from Range table from benthic foraminifers in ODP Hole 189-1170A. 38 records from Range table from benthic foraminifers in ODP Hole 139-856B. 108 records from Phytoplankton abundance off Chao island in Juli 2003, Peru. 20 records from Results of palynological analysis of Hole 302-M0004B. 157 records from Relative abundance of live (Rose Bengal stained) benthic foraminifera of surface sediment off Morocco (Table 6). 149 records from Naturnahes Tal in Siena. 33 records from Benthic macrofauna abundance in surface sediments of the east Greenland continental slope (2000m section). 2 records from The fungus-growing ant genus Apterostigma in Dominican amber.. 206172 records from CM Birds Collection. 834 records from Relativ abundances of dead fauna of benthic foraminifera in surface sediments (Table C2.2). 15 records from Benthic foraminifera assemblages and stable isotopes of sediment core PS2458-4. 51 records from (Table 4) Principal component analysis, paleotemperatures and distribution of infaunal benthic foraminifera in Late Quaternary sediments of core RC09-150 in the southeast Indian Ocean. 3210 records from Ice and animal observations during POLARSTERN cruise ANT-X/6. 4236 records from Collection Porifera SMF. 92982 records from Butterflies - Irish Butterfly Monitoring Scheme. 1387 records from (Figure 6) Dinoflagellate cyst measured on sediment core AI07-12G. 11 records from (Table T6) Relative abundance of Cretaceous plant microfossil taxa of ODP Site 188-1166. 6 records from (Table 1d) Principal petrographic characteristics and K-Ar isotope-geochronological data on samples from the Late Neopleistocene - Holocene activity phase of the Keli Volcanic Highland. 685632 records from Royal Botanic Garden Edinburgh Herbarium (E). 9 records from Abundance of Polychaeta species in surface sediments of the east Greenland continental slope (2000m section). 17450 records from The Scottish Ornithologists' Club - Fife breeding bird tetrad atlas 1991-99. 70222 records from Dorset Environmental Records Centre - Dorset SSSI Species Records 1952 - 2004 (Natural England). 3 records from A Partial Revision of the Genus Metabelba Grandjean (Oribatei, Acarina). 1000 records from Mollusca Specimens of Oiso Municipal Museum. 141 records from Birdrace-Asiola_Quartett-Nordwestmecklenburg. 47 records from Schulgelände Ceciliengymnasium. 3550 records from Herbarium specimens of Institut Scientifique Mohamed V university (RAB). 1582 records from Highland Biological Recording Group - HBRG Badger dataset. 760 records from (Figure 1e) Distribution of planktonic foraminifera in bottom sediments of Core Vy20-3175GC. 1 records from Nothrus pulverulentus. 7 records from (Table 3) Concentrations of brominated flame retardants in adipose tissue of polar bears (Ursus maritimus) between 1991-2007. 1 records from V ° Contributo alla conoscenza dei miriapodi cavernicoli italiani. 1056927 records from Australian Museum provider for OZCAM. 6 records from Taxonomic notes and distribution extension of Durga Das’s leaf-nosed bat Hipposideros durgadasi Khajuria, 1970 (Chiroptera: Hipposideridae) from south India. 1 records from Beitrage zur Kenntniss paläarctischer Myriopoden. XV. Aufsatz: Lithobiiden aus Bosnien, Herzogovina und Dalmatien. 6060 records from Free-living Nematodes from Patagonia coastal lagoons (Chubut, Santa Cruz, Argentina).. 4490 records from Colección Herpetológica del Museo Nacional de Historia Natural de Chile. 284 records from Distribution of planktic foraminifera and stable istopes of sediment core MSM05/5_712-2. 50 records from (Table T3) Biogenic and mineral composition of sediments cored in Hamburg-Wulksfelde. 2473 records from (Table 1) Distribution of planktonic foraminifers at DSDP Hole 90-590A. 60375 records from NZFUNGI - Collections of the New Zealand National Fungal Herbarium (PDD). 766 records from Antarctic Porifera database from the Spanish benthic expeditions: Bentart, Gebrap and Ciemar. 6 records from Fundulopanchax kamdemi (Cyprinodontiformes: Nothobranchiidae) a new species from Korup National Park, western Cameroon.. 26926 records from Colección de Aves de Colombia del Instituto Alexander von Humboldt. 3 records from A new killifish genus and species from the coastal plains of northeastern Brazil (Teleostei: Cyprinodontiformes: Rivulidae).. 40481 records from Biological Records Centre - Soldier Beetle and Jewel Beetle (Coleoptera; Cantharoidea and Buprestoidea) records for Britain and Ireland to 2000 . 30 records from NABU VG Weilerbach - NSG Mehlinger Heide, FFH-Gebiet. 82 records from BIRDRACE Buteo2DO. 103 records from Plasm bearing foraminifera counts of multinet PO200/6_MSN837. 637 records from Countryside Council for Wales - Lamprey Survey Data. 3500 records from Colección Ictiológica de la Universidad de Antioquia. 1 records from On the morphology, biometry and biogeography of Lamtopyxis callistoma (Amoebozoa: Arcellinida). 3 records from (Table 5) Organic matter contents and paleoproductivities at DSDP Site 75-532. 1 records from Pelops auritus. 3321 records from The Pisces Collection at the Staatssammlung für Anthropologie und Paläoanatomie München. 15181 records from British Lichen Society - BLS Lichen Database: Welsh churchyards. 1 records from Die vom k. k. Oberartze Herrn Dr. Justyn Karlinski im Jahre 1887 in Bosnien, der Herzegowina und in Novibazar gesammelten Myriopoden. 78 records from (Table T1) Abundance of dinoflagellate cysts and other palynomorphs in ODP Hole 184-1148A. 4 records from (Appendix A) Nannofossil stratigraphic range chart for the late Maastrichtian section of DSDP Hole 86-577A. 2005 records from EcoRecord - Odonata (Dragonfly and Damselfly) records held by EcoRecord for the Birmingham and the Black Country area collated prior to March 2013. 680 records from (Table 1) Distribution of larger benthic and planktonic foraminifers in ODP Hole 135-841B. 545 records from (Table T2) Planktic foraminiferal assemblages in sediments of ODP Hole 198-1209A, Shatsky Rise, Pacific Ocean. 132 records from Aves Argentinas / Asociación Ornitológica del Plata - Colección de registros observacionales de aves silvestres argentinas - Lista Narosky: familia Fringillidae. 4 records from Simpsonichthys nielseni sp. n. (Teleostei: Cyprinodontiformes: Rivulidae): a new annual killifish from the São Francisco River basin, Brazil.. 1 records from Damaeus concolor. 21 records from "Natur macht Schule 2" Natur im Wohngebiet Gorndorf. 73 records from Chenopodium & Dysphania. 308 records from Record of 7 acritarch taxa, Mg/Ca sea-surface temperatures and palynological preparation data from the Miocene, Pliocene and Pleistocene of IODP Site 303-U1308. 118 records from Birdrace-Birding_Bentheim-Grafschaft_Bentheim. 126 records from Assemblage of living benthic foraminifera in sediment core SO118_MC-43, >125 µm fraction. 874 records from Absolute abundance of dead benthic foraminifera of sediment core M5/2_98MC. 21 records from Assemblage of living benthic foraminifera in sediment core CD145_55830#3, >150 µm. 160 records from Total foraminifera counts of multinet M21/2_MSN658. 218 records from Phytoplankton long-term time-series at the fixed coastal station in the Gulf of Naples, data for the years 2000-2004. Part 2. 28 records from RSPB - Black grouse lek survey in Moray and Nairn 2009 (RSPB). 1614 records from Culture Collection of Algae. 1275 records from (Table T6) Planktonic foraminifera stratigraphy of ODP Hole 198-1209, Zones P12-P18. 7 records from A new species of Trichomycterus (Siluriformes: Trichomycteridae) from south Brazil and redescription of T. iheringi (Eigenmann).. 1900 records from Fungi Collection. 7 records from (Table 5) Concentrations of organochlorine pesticides in adipose tissue of polar bears (Ursus maritimus) between 1991-2007. 212 records from (Appendix A) Campanian-Maastrichtian calcareous nannofossils in DSDP Hole 44-390A. 103 records from Fuchsloch (Mohlsdorf/Ostthüringen). 375 records from Lillachtal mit Kalktuffquelle bei Weißenohe. 54 records from Bäche, Quellen und Teiche im FFH-Gebiet Mühlhauser Halde. 257 records from Seewasen. 80 records from Feldweg Waldkirchen. 31 records from Düpenauwiesen. 42 records from Feuchtwiese Grüne Mitte, Klasse 5a. 192 records from (Table AT1) Grain size distribution and stable isotope record of benthic foraminifera of ODP Hole 175-1085A. 4 records from Nano and microzooplankton abundance and biomass at station NBP97-01-20-3. 114 records from Assemblage of total living benthic foraminifera in sediment core SO118_MC-52. 23 records from Assemblage of living benthic foraminifera in sediment core SO129_MC-09, >125 µm fraction. 112 records from Abundance of dead benthic foraminifera in sediment core CD86_06_BC5. 340 records from Phytoplankton abundance and species composition in the Gulf of Naples from February to December 1987. 127 records from Distribution of planktonic foraminifera of sediment core SH1972_2. 30 records from Nannofossil abundance of Hole 8-71. 2 records from Grenzdenkmal Hötensleben - wo früher Grenze wa(h)r - bewahrte Vielfalt. 255 records from Colecciones Zoológicas de la Universidad de León, Colección de Bivalvos. 85 records from Total foraminifera counts from M35/1_MSN1065. 46 records from Microzooplankton (larger protists and small copepods) abundance measured on concentrated water bottle samples at station PS65/427-6. 10 records from Microzooplankton abundance and biomass at station TT045_19-3. 1 records from Microzooplankton abundance and biomass at station TT050_21-14. 1 records from Microzooplankton abundance and biomass at station TT050_24-13. 10 records from Phytoplankton abundance at station Sechin_2003-12-17_1, Casma, Peru. 191817 records from The Distribution Atlas of Butterflies in Poland. 7 records from Abundance of nematoda in sediment profile M3/1_021 from the Iberian deep sea basin (Table 5). 334 records from (Appendix 2) Stratigraphic distribution of key and potential stratigraphic calcareous nannofossil markers in the upper Campanian-Maastrichtian of ODP Hole 122-762C. 220 records from Assemblage of living benthic foraminifera in sediment core GeoB4917-5. 211 records from Planktic foraminifera counts at CTD station M39/4_404CTD-57. 2 records from Microzooplankton abundance and biomass at station TT050_15-3. 172 records from Benthic foraminiferal number, diversity, and species abundance of size fraction 63-125µm across sapropel S5 in core M40/4_67SL from the lower bathyal of the western Levantine Basin. 14 records from Assemblage of living benthic foraminifera in sediment core CD146_55907#1, 63-150 µm. 148 records from Faunal assemblage of sediment core GS7603-11. 48 records from Plasm bearing foraminifera counts of multinet M27/2_MSN882. 29 records from Content of coarse fraction and G. menardii in sediment corev V26-101. 3 records from Sarcodine counts and carbon biomass at station TT007_15-CTD160. 6 records from Nano and microzooplankton abundance and biomass at station NBP97-01-02-2. 89 records from (Table 3) Dinoflagellate cysts from sediment profile PS1730. 4 records from Phytoplankton abundance at station Rigel_5_2005-08 in August 2005, Chipana, Chile. 167 records from Plasm bearing foraminifera counts from M35/1_MSN1074. 40 records from Plasm bearing foraminifera counts of multinet M21/5_MSN733. 4662 records from The Mammal Society - National Mammal Atlas Project, online recording. 161 records from Total foraminifera counts of multinet M26/1_MSN843. 2342 records from Glasaalmigratie - Glass eel migration in the river Yser. 113 records from Total foraminifera counts of multinet M21/2_MSN627. 16276 records from Coleoptera collection of Uunio Saalas. 56 records from Microzooplankton abundance measured on water bottle samples at station PS58/041-2. 7 records from Abundance of nematoda in sediment profile M3/1_012 from the Iberian deep sea basin (Table 5). 24 records from Abundance, biovolume and biomass of heterotrophic dinoflagellates at station TT008_5-CTD18. 8 records from Distribution of meiobenthos in sediment core M23_122 of the northeastern Atlantic (Table 1). 4 records from Herpetology Collection. 142 records from MfN - Fossil vertebrates I. 322 records from Nannofossil abundance of Hole 15-147. 35 records from Nannofossil abundance of Hole 78-543. 3 records from Nannofossil abundance of Hole 29-283A. 3509 records from Royal Ontario Museum - Entomology (ROME). 85 records from Calcareous nannofossil assemblage in sediment core CIROS-1. 11 records from Nannofossil abundance of Hole 9-83. 91 records from Gemeinschaftsaktion Koordinatoren für nachhaltige Bildung/Wittstocker Grundschulen. 3290 records from (Figure 8) Range chart of selected dinocysts and acritarchs of ODP Hole 104-644A cores 15-35. 435 records from (Table 4) Distribution of calcareous nannofossils from selected samples of ODP Hole 107-654A. 38 records from (Table 7) Pleistocene nannofossil range chart for ODP Hole 134-832A. 980 records from (Appendix 2-5) Distribution of planktonic foraminifera in late Neogene sediments of DSDP Site 31-296 in the western Pacific Ocean. 110 records from (Table A.10) Foraminiferal census data of sediment core PS1243-2 during marine isotopic stage 1-3 (150-500 µm). 23048 records from Herpetology Collection. 63 records from Rund um die Sausenburg. 53976 records from Fish Specimens. 128 records from (Fig. 6, 7) Aragonite preservation of sediment core GeoB2204-2. 10 records from Cyanobacteria, phototrophic and heterotrophic pico-nanoplankton at station TT007_15-CTD152. 16 records from Nannofossil abundance of Hole 9-77B. 9 records from Nannofossil abundance of Hole 75-532. 46 records from Nannofossil abundance of Hole 94-611. 4 records from Abundance of broken diatom frustules measured on water bottle samples at station PS58/038-3. 12 records from Abundance of empty diatom frustules measured on water bottle samples at station PS58/092-3. 88 records from Upper Aptian Niveau Kilian range chart of nannofossils in SE France. 4 records from Nannofossil abundance of Hole 3-16. 17 records from Nannofossil abundance of Hole 85-572D. 14 records from Nannofossil abundance of Hole 85-573. 403 records from Fossil occurrence from planktonic foraminiferas from IODP Hole 315-C0001F. 4 records from Nannofossil abundance of Hole 52-418. 9 records from Nannofossil abundance of Hole 26-250. 5 records from Microplankton abundance at Station MARCH-1997-GN36199704601MSB06 in the euphotic zone of the Aegean Sea in spring 1997. Part 1 - diatoms. 20 records from Meiofauna abundance in sediment core 13200-024. 24 records from Nannofossil abundance of Hole 8-72. 41 records from Nannofossil abundance of Hole 24-238. 8 records from Phytoplankton abundance measured on water bottle samples at station PS65/514-2. 151 records from Biosphärenreservat Mittelelbe. 115 records from Antarctic Pycnogonids II. 20 records from Heavy minerals of sediment core PL94-60. 7560 records from KNWR Entomology Collection. 271 records from Collective List of Descriptions about Bacterial Isolates from Korea. 23 records from Nannofossil abundance of Hole 74-526A. 10 records from Ostracoda abundance of Hole 44-390. 7 records from Nannofossil abundance of Hole 11-101A. 2 records from Smear slide investigation on ODP Hole 205-1254A. 4 records from Abundance of empty diatom frustules measured on water bottle samples at station PS58/107-5. 201526 records from Field Museum of Natural History (Zoology) Insect, Arachnid and Myriapod Collection. 31 records from Projekt Wahner Heide. 1685 records from (Table 18) Distribution of ostracode species in Core PS51/154-11. 8 records from (Table 2g) Nannofossil distribution chart of petroleum well Swan-3. 34 records from sediments composition of surface sediment samples Men4377-7 to Men4418-1. 138 records from RMT Trawl catch from the 1983/84 V5 ADBEX II voyage. 2048 records from (Table 5) Distribution of planktonic foraminifers in ODP Hole 108-659A. 195 records from (Fig. 8g-h, 11) Abundance of planktonic foraminifera and estimation of sea surface temperature and export production of sediment core MD95-2040. 10 records from (Table 2.2.1.1) Abundance of sympagic meiofauna of sea-ice core IO-10. 3 records from Pollen record of profile 3TZ2. 1414 records from Herpetofauna del corredor biológico Chichinautzin y la Sierra de Huautla en el estado de Morelos. 34544 records from Aquatic Heteroptera Recording Scheme - Aquatic Heteroptera Dataset. 5512 records from Vascular Plants Collection of National Museum of Nature and Science. 154124 records from Arizona State University Lichen Collection. 1358 records from Electron Micrograph Database (Australian Antarctic Data Centre). 2427 records from RMT Trawl catch from the 1984/85 V5 SIBEX2 voyage. 106 records from Antarctic Nemertea. 1584 records from (Table 1) Range chart for planktonic foraminifers from ODP Hole 111-667A. 863 records from (Table 2) Distribution chart of dinoflagellate cysts and acritarchs from Angles, Southeast France. 1327 records from (Appendix) Abundances of benthic foraminifera in ODP Hole 105-646B. 27 records from Pliocene/Pleistocene benthic foraminiferal abundances from ODP Hole 161-975D. 1 records from Palynological investigation of surface sample of profile Tso Kar. 3478 records from Especies de peces introducidas en aguas continentales de México. Catálogo y manuscrito. 2814 records from Anfibios y reptiles del estado de Querétaro. 760 records from Arthropoda specimens of Toyama Science Museum. 74 records from (Table 8) Distribution of ostracode species in surface sediments of the eastern Laptev Sea. 80 records from (Table 6) Distribution of the large, few-chambered Globigerinelloides species in the Lesches en Diois section. 165 records from (Table 3) Ostracode distribution in ODP Hole 122-761C. 7323 records from Botanical Research Intitute of Texas. 126 records from (Table 2) Calcareous nannofossil distribution and relative abundance in ODP Hole 114-703A. 1559 records from Plathelminthes - SMF. 277 records from Inventario de gasterópodos terrestres y dulceacuícolas del área focal de Ixcan, Chiapas. 285 records from (Table 1) Distribution of planktonic foraminifera shells of different species in deposits from DSDP Hole 33-315A. 50 records from Distribution of species of planktic foraminifera in bottom sediments from Core AK32-3336. 8577 records from Base de datos sobre la flora de Durango. 50939 records from Instituto Pirenaico de Ecología-CSIC: Herbarium JACA. 323 records from Foraminifera abundance of sediment core IN68-29. 3 records from Analyses of the recent components in the sand fraction of sediment core PS1014-1. 234 records from Antarctic Krill occurrence data from Australian expeditions. 19 records from Schulhof (Bad Waldsee). 15000 records from Computarización de las colecciones de vertebrados terrestres de la Escuela Nacional de Ciencias Biológicas, IPN - Fases 3. 25592 records from Herbario UNAP. 4808 records from North American Sessile Marine Invertebrate Survey. 39 records from Planktic foraminifera abundance of Hole 28-265. 37579 records from Collection Crustacea SMF. 85277 records from University of Ghana - Ghana Herbarium. 534 records from (Appendix B) Total cyst counts, and abundances of Selenopemphix undulata sp. nov. in Pacific Ocean surface samples. 3 records from Akita Prefectural Museum＋Echiurans Specimens of Akita Prefectural Museum. 1634 records from Abundance of benthic infauna in surface sediments from the North Sea sampled during cruise DeHolland1986. 4288 records from Universitat de Girona: HGI-Cormophyta. 197500 records from Museo Nacional de Ciencias Naturales, Madrid: MNCN_ICTIO. 30302 records from Arizona State University Amphibian and Reptile Collection. 1 records from Schulman's Neotropical Adelobotrys database. 38 records from Visual Plants (144.41.33.158) - Plants from Southern Ecuador; Helmut Dalitz. 1429 records from Morano and Cardoso: AraIb. 1086 records from Relative abundance of planktic foraminifera in the 120 kyr time slice reconstruction of sediment core RC17-98. 5 records from Analyses of the recent components in the sand fraction of sediment core PS1222-1. 9187 records from (Table 14) Ranges of benthic foraminifers through the Neogene in ODP Hole 115-714B. 6930 records from (Figure 3) Distribution of planktonic foraminifers in the Upper Cretaceous of DSDP Hole 71-511. 559 records from The Deepwater Program: Northern Gulf of Mexico Continental Slope Habitat and Benthic Ecology - DgoMB: Meiofauna. 9810 records from Royal British Columbia Museum Entomology Collection. 210 records from Donald F. Hooper Butterfly collection, Canada. 163562 records from Bird specimens. 16600 records from Fish Specimens of Museum of Tokushima Prefectural Museum, Japan. 16117 records from Fish Collection. 85720 records from TNHC Herpetology Collection. 41646 records from Coleção Entomológica Paulo Nogueira-Neto - IB/USP. 6926 records from Distribution of planktic foraminifers of core V30-36. 30985 records from MEXU/Asteraceae. 329 records from Fig. 11: Benthic foraminifera assemblage of sediment core MD97-2131. 804 records from Bulk components and planktonic foraminifera of sediment core GeoB3302-1. 21 records from (Table 4) Abundance of Pulleniatina obliquiloculata in sediment core ERDC-112BX. 15470 records from UCM Mammals Collection. 242 records from Landschaftspflegehof (Berlin). 7 records from Microplankton abundance at Station MARCH-1997-GN36199704603MNB05 in the euphotic zone of the Aegean Sea in spring 1997. Part 2 - dinoflagellates. 139 records from Planktic foraminifera assemblage in sediment core GIK23071-3. 1287 records from Percentages of planktonic foraminifera species in sediment core V22-177. 54 records from Occurrence of mammalia relicts at site Rusenschloß. 2294 records from (Table 10C) Occurrences of planktonic foraminifers in selected samples of DSDP Hole 90-588C. 127 records from Foraminifera abundance of Hole 48-405. 11 records from Planktic foraminifera abundance of Hole 67-498. 152 records from Range table from planktonic foraminifers in ODP Hole 146-889A. 1 records from Benthic foraminifera abundance of Hole 96-624. 47 records from Range table from benthic foraminifers in ODP Hole 181-1123C. 710 records from Range table from benthic foraminifers in ODP Hole 172-1054A. 5 records from Analyses of the recent components of sediment core PS1422-1. 29 records from Birkenpilz. 85 records from Planktic foraminifera abundance of Hole 28-264A. 205 records from Planktic foraminifera abundance of Hole 29-284A. 21 records from Sediment fraction analysis and population density of living larger foraminifera in the Persi
Keywords: GBIF; biodiversity; species occurrences